Method for manufacturing injection molded article, and nozzle and injection unit with nozzle for injection molding machine

JP7608543B2Active Publication Date: 2025-01-06ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023140996
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-09
Filing Date
2023-08-31
Publication Date
2025-01-06
Estimated Expiration
2041-06-09

AI Technical Summary

Benefits of technology

【0012】 本発明の一態様によれば、例えば互いに均一分散が難しい複数の配合成分を含む熱可塑性樹脂混合物からであっても、各配合成分の分散均一性に優れる射出成形体を安定的に製造可能な、射出成形体の製造方法、並びに射出成形機用のノズル及びノズル付射出ユニットが提供され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608543000019
    Figure 0007608543000019
  • Figure 0007608543000020
    Figure 0007608543000020
  • Figure 0007608543000021
    Figure 0007608543000021
Patent Text Reader

Abstract

To provide a manufacturing method for an injection molded product, which can stably manufacture an injection molded product with excellent dispersion uniformity of each component, even from a thermoplastic resin mixture containing a plurality of components that are difficult to uniformly disperse, and a nozzle and nozzle injection unit for an injection molding machine.SOLUTION: There is provided a manufacturing method for an injection molded product of a thermoplastic resin mixture that includes a first component containing a thermoplastic resin, and a second component containing one or more substances selected from the group consisting of thermoplastic resins and fillers. The method comprises: a preliminary melted body forming step for obtaining a preliminary melted body containing the first component and second component; an injection melted body forming step for dispersing the second component into the first component in the preliminary melted body to obtain an injection melted body; and an injection step for injecting the injection melted body from an injection port of a nozzle.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an injection molded article, and to a nozzle and an injection unit with a nozzle for an injection molding machine. [Background technology]

[0002] Conventionally, capillary nozzles with various hole diameters are known as nozzles attached to injection molding machines for producing injection molded articles. Capillary nozzles usually have a nozzle hole that is gently tapered toward the capillary part so that the molten material received from the cylinder of the injection molding machine can be guided to the injection port without applying excessive pressure and shear force to the molten material (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-200474 A Summary of the Invention [Problem to be solved by the invention]

[0004] When trying to obtain a molded product made of a thermoplastic resin mixture composed of multiple compounding components, it is necessary to supply materials to the molding machine as homogeneous as possible (for example, materials that have been melt-kneaded and uniformly dispersed in advance in an extruder, etc.). This is because, depending on the type of compounding components, a molding machine with a low resin homogenizing function alone cannot sufficiently increase the dispersion uniformity of the compounding components in the mixture. As an example of homogenization performed in an injection molding machine, a mixture in which a desired amount of a dye-pigment master batch is blended with a base resin is plasticized and molded in the injection molding machine to give the desired color to the entire molded product.

[0005] However, for example, when diluting a master batch highly filled with inorganic filler with its base resin, or when diluting master batches containing different inorganic fillers at different concentrations with a base resin, it is not possible to obtain a uniformly dispersed molded product using an injection molding machine due to the large difference in viscosity between the raw material pellets.

[0006] In other words, when producing an injection-molded article from a thermoplastic resin mixture containing multiple compounding components that are difficult to uniformly disperse with each other, it was necessary to maintain the dispersion state of each compounding component in an ideal state in advance using equipment capable of homogenizing the components by melt kneading, such as an extruder, and to ensure the desired dispersion uniformity before carrying out injection molding.

[0007] However, even if the mixture is melt-kneaded in advance in an extruder or the like to obtain a uniform dispersion, the dispersion state may change due to the coalescence phenomenon of the dispersed phase resin and the dispersed filler due to retention in the cylinder of the injection molding machine, depending on the compatibility state and dispersion state, and this may have an adverse effect of changing the physical properties. This causes a problem that the physical properties of the resulting molded product may change depending on the injection molding machine used. Even if the dispersion state changes due to retention in the molding machine, a technology that can adjust these changes afterwards has been required.

[0008] In addition, when using additives that have low heat resistance and are susceptible to decomposition or crosslinking reactions due to heat during processing, the usual processing method of performing molding after extrusion processing has the problem that the additive components undergo thermal degradation due to multiple thermal histories, making it difficult to fully utilize their performance. Since extrusion processing has the role of uniformly dispersing additives, it applies strong shear, which also adds shear heat, further accelerating the thermal degradation of the additives, making it difficult to fully utilize the additives' performance.

[0009] In this manner, the desired molded body can be obtained by simply mixing a plurality of raw materials or masterbatches to a desired composition at the molding site without using a kneading device such as an extruder, and then molding the mixture in a molding machine. This has the advantages of further reducing the heat history caused by the extrusion process and suppressing deterioration in physical properties, eliminating problems caused by the coalescence of dispersants that may occur during molding retention, and being able to respond to market demands for small-lot, high-mix production in a detailed manner, as well as shortening the process flow and greatly reducing the loss of raw materials used. From this perspective, there has been a strong demand for a technology that can directly obtain a thermoplastic resin molded body with excellent dispersion uniformity from a thermoplastic resin mixture containing a plurality of blending components that are difficult to uniformly disperse with each other in a molding machine.

[0010] The present invention aims to solve the above-mentioned market needs and problems, and to provide a method for producing an injection molded article, which is capable of stably producing an injection molded article having excellent dispersion uniformity of each compound component, even from a thermoplastic resin mixture containing multiple compound components that are difficult to uniformly disperse with each other, as well as a nozzle and a nozzle-equipped injection unit for an injection molding machine. [Means for solving the problem]

[0011] The present invention includes the following aspects. [1] A method for producing an injection-molded article of a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, comprising: a pre-melt forming step of obtaining a pre-melt containing the first component and the second component; A melt forming step of dispersing a second component in the first component in the pre-melt to obtain a melt for injection; and an injection step of injecting the molten material from an injection port of a nozzle; Including, In the step of forming a molten material to be injected, an elongation strain is applied to the pre-molten material to form the molten material to be injected; The method of claim 1, wherein a dispersion diameter of the second component in the injection molded body is smaller than a dispersion diameter of the second component in the pre-melt. [2] A method for producing an injection-molded article of a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, comprising: The method includes a nozzle having a capillary hole having an injection port, and a melt supply fluidly connected to the capillary hole for supplying a melt to be injected, the melt supply comprising: Cross-sectional area change rate = S X / s / 1.4 [In formula: Sx is the cross-sectional area of ​​the melt supply section at a position 1.4 mm from the connection section (mm 2 ) and; s is the cross-sectional area of ​​the capillary hole at the connection (mm 2 ). The cross-sectional area change rate is calculated as 5 mm -1 and using a nozzle, The method comprises: a pre-melt forming step of melting a mixture containing the first component and the second component at a temperature equal to or higher than the melting point of a thermoplastic resin contained in the mixture to obtain a pre-melt; a melt injection forming step of introducing the pre-melt into the melt supply portion of the nozzle to form a melt injection; and an injection step of injecting the molten material for injection from the injection port of the capillary hole at an injection pressure of 40 MPa or more; A method comprising: [3] The method according to claim 2, wherein the nozzle hole diameter in the connecting portion is 4.0 mm or less. [4] The method according to any one of Aspects 1 to 3 above, wherein the method is carried out using an injection molding machine, and the nozzle is a nozzle of the injection molding machine. [5] The nozzle, a capillary hole having an injection port; a melt supply section fluidly connected to the capillary hole for supplying a melt for injection, the melt supply section having a hole wall parallel to the nozzle axis and at an angle of 70° to 100° with respect to a direction toward the upstream of the melt flow; The method according to any one of the above-mentioned aspects 1 to 4, comprising: [6] The nozzle has a capillary hole having an injection port, and a melt supply part fluidly connected to the capillary hole for supplying a melt to be injected; The formula: Pore ​​diameter change rate=D X / d / 1.4 [In formula: Dx is the nozzle hole diameter (mm) of the melt supply part at a position 1.4 mm from the connection part; d is the capillary pore diameter at the junction (mm). The rate of change in hole diameter is calculated as 2 mm -1 The method according to any one of the above-mentioned aspects 1 to 5. [7] The nozzle, a capillary hole having an injection port; The method according to any one of the above aspects 1 to 6, wherein a melt supply section is fluidly connected to the capillary hole section and supplies a melt for injection, and a ratio (l / d) of a capillary hole length l to a capillary hole diameter d at a connection section between the capillary hole section and the melt supply section is 2 or more and 20 or less. [8] The method according to any one of the above aspects 1 to 7, wherein the first component comprises a crystalline resin and the second component comprises an amorphous resin. [9] The method according to any one of Aspects 1 to 8, wherein in the pre-melt forming step, the first component and the second component are supplied separately, and then the first component and the second component are melt-kneaded to form the pre-melt.

[10] The method according to any one of Aspects 1 to 9 above, wherein each of the first component and the second component contains a thermoplastic resin and a filler, and the filler content of the first component and the filler content of the second component are different from each other.

[11] A nozzle attached to a cylinder of an injection molding machine for injecting a thermoplastic resin mixture including a first component including a thermoplastic resin and a second component including one or more selected from the group consisting of a thermoplastic resin and a filler, the nozzle has a capillary hole having an injection port, and a melt supply part fluidly connected to the capillary hole for supplying a melt to be injected; The nozzle hole diameter of the capillary hole portion is 4.0 mm or less, The formula: Cross-sectional area change rate = S X / s / 1.4 [In formula: Sx is the cross-sectional area of ​​the melt supply section at a position 1.4 mm from the connection section (mm 2 ) and; s is the cross-sectional area of ​​the capillary hole at the connection (mm 2 ). The cross-sectional area change rate is calculated as 5 mm -1 Thus, the melt supply is configured to receive a premelt and impart an elongational strain to the premelt to form the melt for injection.

[12] The nozzle according to claim 11, wherein the melt supply section has a hole wall that is parallel to the nozzle axis and has an angle of 70° or more and 100° or less with respect to the direction toward the upstream of the melt flow.

[13] The formula: Pore ​​diameter change rate=D X / d / 1.4 [In formula: Dx is the nozzle hole diameter (mm) of the melt supply part at a position 1.4 mm from the connection part; d is the capillary pore diameter at the junction (mm). The rate of change in hole diameter is calculated as 2 mm -1 The nozzle according to aspect 11 or 12 above.

[14] The nozzle according to any one of the above aspects 11 to 13, wherein a ratio (l / d) of a capillary hole length l to a capillary hole diameter d at a connection portion between the capillary hole and the melt supply portion is 2 or greater and 10 or less.

[15] An injection molding unit with a nozzle attached to an injection molding machine that injects a thermoplastic resin mixture including a first component including a thermoplastic resin and a second component including one or more selected from the group consisting of a thermoplastic resin and a filler, the nozzle-equipped injection molding unit has a nozzle portion and a cylinder portion, the nozzle portion has a capillary hole portion having an injection port, and a melt supply portion fluidly connected to the capillary hole portion and supplying a melt to be injected; The nozzle hole diameter of the capillary hole portion is 4.0 mm or less, The formula: Cross-sectional area change rate = S X / s / 1.4 [In formula: Sx is the cross-sectional area of ​​the melt supply section at a position 1.4 mm from the connection section (mm 2 ) and; s is the cross-sectional area of ​​the capillary hole at the connection (mm 2 ). The cross-sectional area change rate is calculated as 5 mm -1 The nozzle-equipped injection unit is configured as described above, wherein the melt supply section is configured to receive a pre-melt and apply an elongation strain to the pre-melt to form the melt to be injected.

[16] The nozzle-equipped injection unit according to claim 15, wherein the melt supply section has a hole wall that is parallel to the nozzle axis and has an angle of 70° or more and 100° or less with respect to the direction toward the upstream of the melt flow.

[17] The formula: Pore ​​diameter change rate=D X / d / 1.4 [In formula: Dx is the nozzle hole diameter (mm) of the melt supply part at a position 1.4 mm from the connection part; d is the capillary pore diameter at the junction (mm). The rate of change in hole diameter is calculated as 2 mm -1 The nozzle-equipped injection unit according to aspect 15 or 16, as described above.

[18] The nozzle-equipped injection unit according to any one of the above embodiments 15 to 17, wherein a ratio (l / d) of a capillary hole length l to a capillary hole diameter d at a connection portion between the capillary hole and the melt supply portion is 2 or more and 10 or less. Effect of the Invention

[0012] According to one aspect of the present invention, it is possible to provide a method for producing an injection molded article, which is capable of stably producing an injection molded article having excellent dispersion uniformity of each blended component, even from a thermoplastic resin mixture containing multiple blended components that are difficult to uniformly disperse with each other, as well as a nozzle and an injection unit with a nozzle for an injection molding machine. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a nozzle according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a nozzle according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a nozzle according to one embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a nozzle-equipped injection unit according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, exemplary embodiments of the present invention (also referred to as "present embodiments" in this disclosure) will be described, but the present invention is not limited to these embodiments. Note that elements with the same reference numerals in the drawings are intended to have the same configuration or function.

[0015] <Manufacturing method of injection molded body> One aspect of the present invention provides a method for producing an injection-molded article of a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, the method including a pre-melt forming step of obtaining a pre-melt containing the first component and the second component, a melt forming step of forming a melt for injection from the pre-melt, and an injection step of injecting the melt for injection from an injection port of a nozzle.

[0016] When a thermoplastic resin mixture composed of a plurality of blending components is injection molded, the resin and filler dispersed in the preceding extrusion process may aggregate due to retention in the molding machine, making it difficult to stabilize the performance. When a master batch highly filled with inorganic filler is to be diluted only by the molding machine, it may be difficult to uniformly disperse the blending components depending on the type and concentration of the blending components, and the design of the conditions of the injection molding machine to achieve the desired uniformity of dispersion may become complicated, or even if such complicated design of conditions is used, the desired uniformity of dispersion may not be achieved. The present inventors have investigated various methods for stably producing injection molded articles with excellent uniformity of dispersion, even for thermoplastic resin mixtures containing blending components that are difficult to uniformly disperse, and have unexpectedly found that the dispersion state of the blending components in the melt can be further improved by controlling the flow of the melt of the thermoplastic resin mixture in the vicinity of the injection nozzle. Furthermore, they have found that by adopting such a method, the thermal history of the material can be reduced and unexpected physical properties can be expressed.

[0017] By controlling the flow of the molten material in the vicinity of the injection nozzle in this manner, it is possible to stably produce an injection molded article having excellent dispersion uniformity of each blended component even from a thermoplastic resin mixture containing multiple blended components that are difficult to uniformly disperse with each other. In one aspect, the method of the present embodiment is carried out using an injection molding machine, and the nozzle used is the nozzle of the injection molding machine.

[0018] In one embodiment, in the step of forming a melt for injection, an elongational strain is applied to the pre-melt to form the melt for injection. In one embodiment, the pre-melt includes a first and a second component, and in one embodiment, is composed of two or more phases having one or more dispersed phases. Applying an elongational strain to the pre-melt results in a change in the dispersion form (e.g., phase separation form) due to elongational deformation of the melt, which contributes to reducing the dispersion size and improving the dispersion uniformity. In one embodiment, the second component forms one or more phases in the pre-melt, and the dispersion diameter of the second component in the injection molded body is smaller than the dispersion diameter of the second component in the pre-melt. When the second component is composed of two or more phases (for example, when the second component includes a thermoplastic resin and a filler and each of them forms a phase), the dispersion diameter of each phase (in the case of the filler, the aggregate particle diameter) can be smaller in the injection molded body than in the pre-melt. In one embodiment, the dispersion size of the second component of the present disclosure is the number average particle size (for thermoplastic resins) or average aggregate size (for fillers) measured by a method described in the Examples section of this disclosure or a method understood to be equivalent thereto by one of ordinary skill in the art.

[0019] When the second component is a thermoplastic resin, the dispersed particle size of the dispersed phase in the raw material pellets described in the [Examples] section of this disclosure can be regarded as the dispersed particle size of the second component in the pre-melt, because the dispersed particle size of the second component in the pre-melt does not change from the dispersed particle size of the second component in the raw material pellets.

[0020] The dispersion diameter of the thermoplastic resin as the second component can be determined by the number average particle diameter and / or particle diameter distribution. The dispersion diameter can be compared at the upper limit (i.e., maximum diameter) or the lower limit (i.e., minimum diameter) of the particle diameter distribution. In one embodiment, it is desirable to compare the dispersion diameter by the number average particle diameter.

[0021] The comparison of the dispersed particle diameter of the thermoplastic resin in the pre-melt and the dispersed particle diameter of the thermoplastic resin in the injection-molded body can be carried out by comparing the number average particle diameter of the dispersed phase in the raw material pellets with the number average particle diameter of the dispersed phase in the injection-molded piece, as described in the [Examples] section of this disclosure.

[0022] When the second component is a filler, the aggregate diameter of the filler (CNF, etc.) in the raw material pellets described in the [Examples] section of this disclosure can be regarded as the dispersed diameter of the second component in the pre-melt, because the aggregate diameter as the dispersed diameter of the second component in the pre-melt does not change from the aggregate diameter as the dispersed diameter of the second component in the raw material pellets.

[0023] The aggregate size of the filler as the second component as a dispersion size can be determined by the average aggregate size and / or the aggregate size distribution. The aggregate sizes can be compared at the upper limit or lower limit of the aggregate size distribution. In one embodiment, it is desirable to compare the aggregate sizes by the average aggregate size.

[0024] The comparison of the dispersion diameter of the filler in the pre-melt and the dispersion diameter of the filler in the injection-molded body can be carried out by comparing the average agglomerate diameter of the filler in the raw material pellets and the average agglomerate diameter of the filler in the injection-molded piece, as described in the [Examples] section of this disclosure.

[0025] The ratio of the dispersion diameter in the injection molded body to the dispersion diameter in the pre-melt of the second component (the ratio for each phase when the second component has two or more phases) may be 0.90 or less, or 0.85 or less, or 0.80 or less, or 0.70 or less, or 0.60 or less, or 0.50 or less in one embodiment from the viewpoint of obtaining an injection molded body having a small dispersion size and excellent dispersion uniformity, and may be 0.01 or more, or 0.05 or more, or 0.10 or more in one embodiment from the viewpoint of ease of manufacture of the injection molded body. In one embodiment, the ratio being 0.90 or less may be an indicator that an elongation strain has been imparted to the pre-melt.

[0026] <Components of thermoplastic resin mixture> The thermoplastic resin mixture includes a first component and a second component. The first component includes a thermoplastic resin. The first component may further include a filler in addition to the thermoplastic resin. The filler may be an organic filler or an inorganic filler, or a combination thereof. Examples of organic fillers include cellulose (e.g., cellulose nanofibers, cellulose whiskers, cellulose microfibers, etc.), organic-containing carbon fillers (carbon black, carbon fibers, etc.), various synthetic polymers, etc. Examples of inorganic fillers include glass fibers, zeolites, ceramics, talc, mica, titanium dioxide, silica, wollastonite, dragonite, calcium carbonate, metal powders, etc.

[0027] According to one aspect of the present invention, even when a filler that is generally difficult to uniformly disperse in a resin is used, an injection molded article with excellent dispersion uniformity can be produced. Therefore, when the filler contains a filler that is generally difficult to uniformly disperse in a resin (e.g., cellulose nanofiber), the advantages of the present invention are more prominent and are preferable.

[0028] The first component may contain various additives (e.g., compatibilizers, plasticizers, colorants, fragrances, pigments, flow control agents, leveling agents, conductive agents, antistatic agents, UV absorbers, UV dispersants, deodorizers, etc.) in addition to the thermoplastic resin and any filler.

[0029] The second component includes one or more selected from the group consisting of a thermoplastic resin and a filler. Specific examples of the thermoplastic resin and the filler may be the same as those exemplified in the first component.

[0030] The second component may further include various additives in addition to one or more selected from the group consisting of a thermoplastic resin and a filler. The additives that the second component may include may be the same as those exemplified as the additives in the first component.

[0031] The combination of the first component and the second component can be selected in various ways depending on the purpose. The method of this embodiment can form an injection molded product with excellent dispersion uniformity of the blended components even when the affinity between the first component and the second component is low. For example, the first component may contain a crystalline resin and the second component may contain an amorphous resin. The affinity between the crystalline resin and the amorphous resin is generally low, but the method of this embodiment can produce an injection molded product with excellent dispersion uniformity. For example, each of the first component and the second component may contain a thermoplastic resin and a filler, and the filler content of the first component and the filler content of the second component (which may be the same or different from the filler in the first component) may be different from each other.

[0032] The thermoplastic resin mixture may further include an additional component in addition to the first component and the second component. Examples of the additional component include: a thermoplastic resin having a different type and / or properties from the thermoplastic resin contained in the first component and the thermoplastic resin that may be contained in the second component; and / or a filler having a different type and / or properties from the filler that may be contained in the first component and / or the second component. In one embodiment, the thermoplastic resin mixture may be composed of only the first component and the second component.

[0033] Further detailed preferred embodiments of the thermoplastic resin and the organic and inorganic fillers will be described later.

[0034] <Nozzle> Next, a nozzle preferably used in the method of the present embodiment will be described. Figures 1 to 3 are cross-sectional schematic diagrams showing a nozzle according to one aspect of the present invention. With reference to Figures 1 to 3, the method of the present embodiment may use nozzles 11, 21 (also referred to as capillary nozzles in this disclosure) having a capillary hole 1 having an injection port P and a melt supply part 2 fluidly connected to the capillary hole 1 and supplying a melt for injection. In one aspect, the capillary nozzle is attached to an injection molding machine.

[0035] With reference to FIG. 3, in one embodiment, the capillary nozzle comprises a capillary having the formula: Cross-sectional area change rate = S X / s / X [In formula: S x is the cross-sectional area of ​​the melt supply section at a position X mm from the connection section (mm 2 ) and; s is the cross-sectional area of ​​the capillary hole at the connection (mm 2 ) and; X is the distance from the connecting portion C between the capillary hole 1 and the melt supply portion 2 toward the upstream side of the melt flow in the nozzle axial direction (the direction of the arrow U in the figure), specifically 1.4 mm. The cross-sectional area change rate is calculated as 5 mm -1 This is the nozzle. Note that in FIG. 3, the dimension X is greatly exaggerated for ease of understanding.

[0036] When the cross-sectional area change rate is increased (i.e., the cross-sectional area of ​​the melt supply section 2 is rapidly reduced toward the downstream side of the melt flow), the pre-melt is elongated and subjected to elongational strain (also called elongational strain), which applies a high shear force to the pre-melt and improves the dispersion state of the blended components in the pre-melt. -1 From the viewpoint of satisfactorily realizing the effect of improving the dispersion state of the blended components, it is preferable that the cross-sectional area change rate is 8 mm or more. -1 or more, or 10mm -1 or more, or 20mm -1 On the other hand, if the cross-sectional area change rate is excessively high, resin retention areas may occur and carbonization may occur. Therefore, the cross-sectional area change rate is preferably 300 mm -1 Less than or equal to 200mm -1 Less than or equal to 150mm -1 The flow passage cross-sectional area for calculating the cross-sectional area change rate is calculated from the nozzle hole diameter.

[0037] The capillary hole diameter (d) in the connecting portion C is important for elongationally flowing the pre-melt and imparting elongational strain thereto. From the viewpoint of stably achieving fine dispersion of the dispersant, it is preferably 4.0 mm or less, or 3.0 mm or less, or 2.5 mm or less, or 2.0 mm or less, or 1.8 mm or less. Moreover, from the viewpoint of suppressing application of excessive injection pressure, it may be preferably 0.1 mm or more, or 0.2 mm or more, or 0.4 mm or more, or 0.6 mm or more, or 0.8 mm or more, or 1.0 mm or more.

[0038] Next, the nozzle hole diameter at the injection port P may be equal to or larger than the capillary hole diameter at the connecting portion C, but is preferably 1 mm or more, or 1.5 mm or more, or 2 mm or more. Also, it may be preferably 10 mm or less, or 6 mm or less, or 5 mm or less, or 4 mm or less, or 3 mm, according to the spool tip diameter of the molded product.

[0039] From the viewpoint of causing a diameter elongation flow by a sudden contraction of the flow path at the connecting portion C, referring to Fig. 3, a preferred embodiment of the ratio (l / d) of the capillary hole length l to the capillary hole diameter d at the connecting portion C between the capillary hole of the capillary nozzle and the melt supply portion is 2 or more and 20 or less. From the viewpoint of aligning the flow direction of the melt for injection to form a uniform injection-molded product, the above ratio (l / d) is preferably 2 or more, or 3 or more, or 5 or more, and from the viewpoint of preventing the application of excessive pressure and performing injection molding stably and easily, the ratio is preferably 20 or less, or 10 or less, or 8 or less, or 7 or less.

[0040] The capillary hole portion 1 may have the same hole diameter over the entire area, or the nozzle hole diameter at the injection port P may be larger than the capillary hole diameter at the connection portion C. That is, the molten resin passes from the upstream side of the melt flow through the nozzle hole at the connection portion C to the nozzle hole outlet at the injection port P, and the capillary hole passing through during this process may be a straight tube with a constant diameter, or may be a trumpet-shaped tube with a gradually increasing diameter. A more preferable embodiment is an embodiment in which the capillary hole diameter at the connection portion C is maintained at least for a length corresponding to the capillary hole diameter at the connection portion C, and then gradually widened to the diameter of the nozzle hole at the injection port P. From the viewpoint of suppressing turbulence of the resin flow, the maintained length is preferably 1.5 times or more, 2 times or more, or 5 times or more of the length corresponding to the capillary hole diameter at the connection portion C, and from the viewpoint of reducing the applied pressure and facilitating injection molding, it is preferably 10 times or less, 7 times or less, or 6 times or less.

[0041] 1 and 2, in one embodiment, the nozzle 11, 21 has a capillary hole 1 having an injection port P, and a melt supply part 2 for supplying a melt for injection, which is fluidly connected to the capillary hole 1, and has a hole wall W having an angle θ of 70° to 100° with respect to a direction parallel to the nozzle axis and toward the upstream of the melt flow (the direction of the arrow U in the figure). In this case, the angle θ may be 70° to 100° at any part of the melt supply part 2, but in a preferred embodiment, the angle of the part of the melt supply part 2 that contacts the connecting part C (i.e., the rising angle of the hole wall of the melt supply part) is 70° to 100°. In a conventional capillary nozzle having a capillary hole with approximately the same hole diameter and a melt supply part connected thereto and having a hole diameter larger than that of the capillary hole, the hole diameter of the melt supply part is gradually decreased toward the capillary hole (i.e., has a tapered shape), so that the melt received from the cylinder is guided to the injection port without receiving excessive pressure or shear force. On the other hand, in the melt supply part 2 having the hole wall W with the above angle θ (i.e., a steep hole wall nearly perpendicular to the flow path direction), the pre-melt is subjected to extremely large elongation strain when it flows toward the capillary hole part 1. This elongation strain can have the effect of dispersing the blended components in the melt more uniformly. In this way, the melt supply part 2 having the hole wall W with the above angle θ has the advantage of being able to form a melt for injection in which the blended components are dispersed extremely uniformly. The angle θ is preferably 75° or more, or 80° or more, or 82° or more, or 84° or more, or 85° or more. The angle θ may be an acute angle (i.e., 70° or more and less than 90°) as shown in Fig. 2, but an angle of 90° or more as shown in Fig. 1 may be preferable in that an extremely large elongation strain is imparted to the pre-molten material in the melt supplying section 2. However, from the viewpoint of suppressing resin retention in the nozzle and generation of black spots, the angle θ is preferably 100° or less, 95° or less, or 90° or less.

[0042] Referring to FIG. 3, in one embodiment, the capillary nozzle has the following formula: Pore ​​diameter change rate=DX / d / X [In formula: Dx is the nozzle hole diameter (mm) of the melt supply part at a position X mm from the connection part; d is the capillary pore diameter at the junction (mm); X is the distance from the connecting portion C between the capillary hole 1 and the melt supply portion 2 toward the upstream side of the melt flow in the nozzle axial direction (the direction of the arrow U in the figure), specifically, 1.4 mm.] The rate of change in hole diameter is calculated as 2 mm -1 That's all.

[0043] When the rate of change in the hole diameter is increased (i.e., the nozzle hole diameter of the melt supplying section 2 is rapidly reduced toward the downstream side of the melt flow), similarly to the case of increasing the rate of change in the cross-sectional area, the pre-melt is subjected to elongational flow to impart elongational strain, and a high shear force is applied to the pre-melt, improving the dispersion state of the blended components in the pre-melt. -1 From the viewpoint of satisfactorily realizing the effect of improving the dispersion state of the blended components, it is preferable that the cross-sectional area change rate is 2.5 mm -1 or more, or 3mm -1 or more, or 4mm -1 On the other hand, if the rate of change in hole diameter is excessively high, resin retention portions may occur and carbonized matter may be generated. Therefore, from the viewpoint of stably injecting the molten material for injection from the injection port, the rate of change in hole diameter is preferably 20 mm or less. -1 Less than or equal to 15mm -1 Less than or equal to 10mm -1 It may be the following:

[0044] <Injection unit with nozzle> FIG. 4 is a schematic cross-sectional view showing a nozzle-equipped injection unit according to one embodiment of the present invention. Referring to FIG. 4, in the method of this embodiment, a nozzle-equipped injection molding unit 40 attached to an injection molding machine may be used. The nozzle-equipped injection molding unit 40 may have a nozzle portion 41 and a cylinder portion 42, and the nozzle portion 41 may be the capillary nozzle of the present disclosure as described above. The cylinder portion 42 may have a general configuration known to those skilled in the art as a cylinder of an injection molding machine, and may be configured to include members such as a plunger, a screw, a check valve, and a heater, and to transfer the molding material supplied from the hopper to the nozzle portion in a desired state (amount, temperature, pressure, etc.). Note that FIG. 4 shows an example in which the nozzle portion 41 and the cylinder portion 42 are separate members, but the nozzle portion 41 and the cylinder portion 42 may be a single member.

[0045] <Each step in the manufacturing method of injection molded articles> Hereinafter, an example of each step in the method for producing an injection molded article from a thermoplastic resin mixture according to one embodiment of the present invention will be described.

[0046] [Pre-melt formation process] In this step, a pre-melt containing a first component and a second component is obtained. (1) A method in which a kneaded mixture obtained by previously kneading the first component and the second component is subjected to a preliminary melt forming step, or (2) A method in which the first component and the second component are separately subjected to a pre-melt forming step, and then melt-kneaded to form a pre-melt; etc.

[0047] In the case of (1) above, the kneading conditions include processing with a single screw extruder, twin screw extruder, multi-screw extruder, sheet extruder, kneader, Brabender, plastomill, continuous high shear processing machine, and rollers. Processing conditions such as temperature vary depending on the properties of the first component and the second component, but conditions that are common to those skilled in the art can be applied without any problems. For example, the temperature is preferably set to match the resin that starts to flow at the highest temperature among the thermoplastic resins used. Examples of combinations of the first component and the second component include a polymer alloy of thermoplastic resin A and another thermoplastic resin, a composite of thermoplastic resin A and fillers, and a composite of a thermoplastic resin polymer alloy and fillers, but are not limited to these as long as the first component contains a thermoplastic resin and the second component contains one or more selected from the group consisting of thermoplastic resins and fillers.

[0048] In the above case (1), the conditions for the pre-molten body forming step can be exemplified by introducing a mixture obtained by previously kneading the first and second components into an injection molding machine, and forming a pre-molten body by shearing with the screw of the molding machine. The temperature set in this case is desirably set to match the resin that starts to flow at the highest temperature among the thermoplastic resins used. In the case of a pre-plastication type injection molding machine, the step of melt-kneading with the screw, introducing the melt into the plunger region, and measuring it is also included in this step.

[0049] The above (2) is a method in which the first component and the second component are separately subjected to the pre-melt forming step. A specific example of this is a step in which at least a thermoplastic resin is separately supplied as the first component, and a component containing one or more selected from the group consisting of a thermoplastic resin and a filler is separately supplied as the second component to form a pre-melt. Among these, the first component may be a kneaded product obtained by previously kneading a thermoplastic resin with other components (other thermoplastic resins and / or fillers, etc.) using a processing machine or the like described in detail in the above (1). The second component may be a kneaded product obtained by previously kneading a thermoplastic resin with other components (other thermoplastic resins and / or fillers, etc.) selected from the same or different thermoplastic resin as the first component, organic and / or inorganic fillers, or a kneaded product obtained by previously kneading a thermoplastic resin with other components (other thermoplastic resins and / or fillers, etc.). Specific examples of the first component include, but are not limited to, a thermoplastic resin A alone, a resin composition in which a stabilizer or the like is blended in advance with a thermoplastic resin A, a polymer alloy of a thermoplastic resin A and another thermoplastic resin, a composite of a thermoplastic resin A and fillers, a composite of a thermoplastic resin polymer alloy and fillers, etc. Specific examples of the second component include, but are not limited to, a thermoplastic resin B alone, a resin composition in which a stabilizer or the like is blended in advance with a thermoplastic resin B, a polymer alloy of a thermoplastic resin B and another thermoplastic resin including a thermoplastic resin A, a composite of a thermoplastic resin B and fillers, a composite of a thermoplastic resin polymer alloy and fillers, etc. In addition, it is also possible that the first component is a composition consisting of a thermoplastic resin A and another component, and a thermoplastic resin A is used as the second component to dilute it. In any case, as long as it is a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, it is not limited to these. The conditions for the pre-melt forming step here may be the same as those in (1) above.

[0050] In one embodiment, this step involves melting the mixture containing the first component and the second component at a temperature equal to or higher than the melting point of the thermoplastic resin contained in the mixture (the highest melting point when there are multiple thermoplastic resins having melting points) to obtain a pre-molten body. Such melting conditions are advantageous in terms of obtaining an injection molded body with excellent dispersion uniformity. The difference between the melting temperature (°C) of the mixture and the above-mentioned melting point (°C) (i.e., melting temperature (°C) - melting point (°C)) is preferably equal to or higher than the above-mentioned melting point, or +5°C or higher, or +10°C or higher, in terms of the pre-molten body having good fluidity and thus facilitating improvement of dispersion uniformity, and may be +70°C or lower, or +60°C or lower, or +50°C or lower, in terms of the tendency of elongational strain to occur. The melting temperature here may be the set temperature in the step of obtaining the pre-molten body.

[0051] [Injection melt forming process] In this step, a melt to be injected is obtained from the pre-melt. In one embodiment, the step of forming the melt to be injected is carried out by introducing the pre-melt into the melt supply portion of the capillary nozzle.

[0052] In one embodiment, in the melt for injection forming step, the first component and the second component in the pre-melt are dispersed with each other to obtain the melt for injection. Here, dispersing the first component and the second component with each other means improving the dispersion state of the first component and the second component, more specifically, reducing the dispersion size and / or improving the dispersion uniformity of at least one blended component in the first component and / or the second component. In one embodiment, the melt for injection is obtained by dispersing the second component in the first component in the pre-melt. The improvement in the dispersion state can be confirmed, for example, in the case of improvement in the dispersibility between thermoplastic resins, by preparing a slice and measuring the size of the dispersed phase before and after the melt for injection forming step using an optical microscope, a transmission electron microscope, or the like. For example, if etching can be performed using a solvent that dissolves the measurement target component, which is the dispersed phase, but does not dissolve the continuous phase component, the sample after the treatment can be confirmed with a laser microscope or a scanning electron microscope. In addition, for example, it is possible to dissolve the continuous phase resin using a solvent that dissolves the continuous phase component but does not dissolve the dispersed phase component to be measured, and to measure the diameter of the dispersed phase using a laser granulometer. In addition, for example, in the case of improving the dispersibility of a filler in a thermoplastic resin, a method of preparing a slice and using an optical microscope, a transmission electron microscope, or the like to actually measure the dispersion state of the filler before and after the melt for injection forming process, or a method of non-destructively measuring the dispersion state of the filler inside using an X-ray CT measuring device, methods well known to those skilled in the art can be applied. There are various methods, but it is desirable to adopt the same measurement method at least for confirming the change in the dispersion state before and after the melt for injection forming process.

[0053] Examples of a method for dispersing the first component and the second component in each other (in one embodiment, dispersing the second component in the first component) include a method of imparting elongational strain and / or shear strain to a pre-molten body, and these may include a method of imparting elongational strain to a pre-molten body by using a capillary nozzle of the present disclosure, a method of performing injection molding at an extremely high injection speed of more than 1000 mm / sec using a special ultra-high speed injection molding machine, and a method of plasticizing a composition having a high filler content and high melt viscosity while applying a high back pressure during plasticization in a molding machine.

[0054] In this step, in one embodiment, an elongational strain is applied to the pre-melt to form a melt for injection. The elongational strain can be applied to the pre-melt by increasing the flow rate per unit cross-sectional area of ​​the pre-melt, and in one embodiment, such a flow rate can be achieved by using a nozzle having a unique configuration according to the present disclosure, or by controlling the shear rate and / or injection pressure during injection, which will be described later. Therefore, in one embodiment, whether or not an elongational strain is applied to the pre-melt can be determined by the magnitude of the rate of change in the capillary cross-sectional area and the injection speed.

[0055] [Injection process] In this step, the molten material for injection is injected into the cavity of the mold from the injection port of the nozzle (in one embodiment, the capillary hole of the capillary nozzle). From the viewpoint of producing an injection molded article having excellent dispersion uniformity of the blended components, particularly from the viewpoint of favorably generating elongational strain, the apparent shear rate (SR) during injection is preferably 5,000 s -1 or more, or 10,000 seconds -1 or more, or 50,000 seconds -1 or more, or 100,000 seconds -1 From the viewpoint of stable injection from the injection port, it is preferable to perform the injection for 5,000,000 seconds or more. -1 Less than or equal to 3,000,000 seconds -1 Less than or equal to 2,000,000 seconds -1 The apparent shear rate is a value expressed by the following formula, and can be controlled by the injection speed of the injection molding machine (screw movement speed, piston movement speed in the case of a pre-plasticization type injection molding machine). Apparent shear rate SR=32Q / (π d 3 ) where Q is the ejection volume per second (mm 3 / sec), and d represents the capillary pore diameter (mm) at the connecting portion C.

[0056] The injection pressure in the injection step is preferably 40 MPa or more, or 50 MPa or more, or 60 MPa or more, or 70 MPa or more from the viewpoint of producing an injection molded article having excellent dispersion uniformity of the blended components, particularly from the viewpoint of favorably generating elongation strain. A higher injection pressure is preferable, but from the viewpoint of suppressing heat generation at the nozzle, in one embodiment, the injection pressure may be 200 MPa or less, 180 MPa or less, or 170 MPa or less. In one embodiment, the above injection pressure is the maximum injection pressure of the injection molding machine.

[0057] <Thermoplastic resin> The thermoplastic resin contained in the first component and the thermoplastic resin that may be contained in the second component include a crystalline resin having a melting point within a range of 100°C to 350°C, or an amorphous resin having a glass transition temperature within a range of 100°C to 250°C, and a thermoplastic elastomer that has a glass transition temperature below room temperature (23°C) and exhibits elasticity at room temperature.

[0058] The melting point of a crystalline resin here refers to the peak top temperature of the endothermic peak that appears when the temperature is raised from 23°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), and when two or more endothermic peaks appear, it refers to the peak top temperature of the endothermic peak on the highest temperature side. When measuring, it is desirable to use a sample that is first heated to a temperature condition of the melting point + 20°C or more to melt the resin, and then cooled to 23°C at a heating rate of 10°C / min.

[0059] The glass transition temperature of the amorphous resin and the thermoplastic elastomer referred to here means, unless otherwise specified, the peak top temperature at which the storage modulus significantly decreases and the loss modulus becomes maximum when measured using a dynamic viscoelasticity measuring device while increasing the temperature at a rate of 2°C / min from 23°C for the amorphous resin and from -150°C for the thermoplastic elastomer, and applying a frequency of 10 Hz. When two or more peaks of the loss modulus appear, in the case of the amorphous resin, it means the peak top temperature of the peak on the highest temperature side, and in the case of the thermoplastic elastomer, it means the peak top temperature of the peak on the lowest temperature side.

[0060] Examples of the thermoplastic resin that may be contained in the first component and the second component include at least one selected from the group consisting of olefin resins, styrene resins, polyesters, polyamides, polyphenylene ethers, polyacetals, polyphenylene sulfides, polyarylates, polyetherimides, polyethersulfones, polysulfones, polyaryl ketones, block copolymers of aromatic vinyl compounds and conjugated diene compounds, partially hydrogenated products of block copolymers of aromatic vinyl compounds and conjugated diene compounds, and mixtures thereof.

[0061] More specifically, at least one selected from the group consisting of polyethylene resins, polypropylene resins, homopolystyrene, rubber-modified polystyrene, acrylonitrile-styrene copolymers, copolymers of N-phenylmaleimide and styrene, polyamides, polyphenylene ethers, polyarylene sulfides, polyarylates, polyetherimides, polyethersulfones, polysulfones, liquid crystal polyesters, polyaryl ketones, block copolymers of aromatic vinyl compounds and conjugated diene compounds, partially hydrogenated products of block copolymers of aromatic vinyl compounds and conjugated diene compounds, and mixtures thereof may be mentioned. The details will be explained below.

[0062] (Olefin resin) In the present embodiment, examples of olefin-based resins include polyethylene, polypropylene, copolymers of ethylene and α-olefins, and copolymers of ethylene and acrylates, and polypropylene (hereinafter sometimes simply abbreviated as "PP") is preferred.

[0063] Examples of polypropylene include: propylene homopolymer; propylene-ethylene block copolymers having a propylene homopolymer portion and a propylene-ethylene random copolymer portion, which are obtained by obtaining a propylene homopolymer and then copolymerizing the propylene homopolymer with propylene, ethylene and / or at least one other α-olefin (e.g., 1-butene, 1-hexene, etc.); etc. The polypropylene may be a mixture of a propylene homopolymer and a propylene-ethylene block copolymer.

[0064] In this embodiment, the density of the propylene polymer portion of the polypropylene is usually 0.90 g / cm 3 or more, 0.90 to 0.93 g / cm 3 and preferably 0.90 to 0.92 g / cm 3 It is more preferable that the density of the propylene polymer portion is determined by the JIS K-7112 water substitution method. When the polypropylene is a copolymer of propylene and an α-olefin, the copolymerization component is extracted using a solvent such as hexane, and the density of the remaining propylene polymer portion is determined by the above-mentioned JIS K-7112 water substitution method.

[0065] In the present embodiment, it is also effective to add a known crystal nucleating agent to increase the density of polypropylene. The crystal nucleating agent is not particularly limited as long as it improves the crystallinity of polypropylene, but examples of the crystal nucleating agent include organic nucleating agents such as metal salts of aromatic carboxylic acids, sorbitol derivatives, organic phosphates, and aromatic amide compounds, and inorganic nucleating agents such as talc.

[0066] In the present embodiment, the melt flow rate (MFR) of the polypropylene (based on JIS K-6758: 230°C, 21.2 N load) is preferably 10 g / 10 min or more, more preferably 20 to 50 g / 10 min, even more preferably 25 to 40 g / 10 min, and even more preferably 30 to 40 g / 10 min, from the viewpoint of improving injection moldability.

[0067] (styrene resin) Examples of styrene-based resins include homopolystyrene, rubber-modified polystyrene (commonly known as high-impact polystyrene), styrene-butadiene block copolymers and / or hydrogenated products thereof, styrene-isoprene block copolymers and / or hydrogenated products thereof, and copolymers of styrene and vinyl monomers radically copolymerizable with the styrene.

[0068] Specific examples of vinyl monomers radically copolymerizable with styrene include vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; vinyl carboxylic acids and esters thereof such as acrylic acid, butyl acrylate, methacrylic acid, methyl methacrylate, and ethylhexyl methacrylate; unsaturated dicarboxylic anhydrides and derivatives thereof such as maleic anhydride and N-phenylmaleimide; and diene compounds such as butadiene and isoprene. It is also possible to copolymerize two or more of these in combination.

[0069] From the viewpoint of commercial availability, preferred styrene resins include homopolystyrene, rubber-modified polystyrene, acrylonitrile-styrene copolymer, N-phenylmaleimide-styrene copolymer, and mixtures thereof.

[0070] From the viewpoint of maintaining a balance between the fluidity of the melt and the mechanical strength of the resulting injection-molded article, the homopolystyrene and rubber-modified polystyrene are preferably those having a reduced viscosity (measured in a 30°C toluene solution at a concentration of 0.5 g / 100 ml) in the range of 0.5 to 2.0 dl / g. The reduced viscosity of the homopolystyrene and rubber-modified polystyrene is more preferably 0.7 dl / g or more, and even more preferably 0.8 dl / g or more. The reduced viscosity of the homopolystyrene and rubber-modified polystyrene is preferably 1.5 dl / g or less, and more preferably 1.2 dl / g or less.

[0071] From the viewpoint of chemical resistance and heat resistance of the resulting resin molded article, the acrylonitrile-styrene copolymer is preferably a copolymer containing 3 to 30% by mass of acrylonitrile structural units. In the copolymer, the content of acrylonitrile structural units is more preferably 5% by mass or more, and even more preferably 7% by mass or more. Moreover, the content of acrylonitrile structural units is more preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less.

[0072] The acrylonitrile-styrene copolymer may be a copolymer obtained by copolymerizing 30 parts by mass or less of butadiene with respect to 100 parts by mass of the total of acrylonitrile and styrene.

[0073] From the viewpoint of the heat resistance of the resulting resin molded article, the N-phenylmaleimide-styrene copolymer is preferably a copolymer containing 15 to 70% by mass of N-phenylmaleimide structural units. The content of the N-phenylmaleimide structural units is more preferably 20% by mass or more, and even more preferably 25% by mass or more. The content of the N-phenylmaleimide structural units is more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less.

[0074] The N-phenylmaleimide-styrene copolymer may be a copolymer in which 30 parts by mass or less of acrylonitrile is further copolymerized with respect to a total of 100 parts by mass of N-phenylmaleimide and styrene.

[0075] From the viewpoint of maintaining the heat resistance of the resulting resin molded article, the glass transition temperature of the N-phenylmaleimide-styrene copolymer is preferably in the range of 140° C. to 220° C. The above glass transition temperature is a value measured with a differential scanning calorimeter (DSC) at a heating rate of 20° C. / min.

[0076] (polyester) Examples of polyesters include polybutylene terephthalate, polypropylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polypropylene naphthalate, and liquid crystal polyesters, and among these, liquid crystal polyesters are preferred. Liquid crystal polyesters are polyesters called thermotropic liquid crystal polymers. Thermotropic liquid crystal polymers are not particularly limited, but include, for example, thermotropic liquid crystal polyesters having p-hydroxybenzoic acid, alkylene glycol, and terephthalic acid as main constituent units, thermotropic liquid crystal polyesters having p-hydroxybenzoic acid and 2-hydroxy-6-naphthoic acid as main constituent units, and thermotropic liquid crystal polyesters having p-hydroxybenzoic acid, 4,4'-dihydroxybiphenyl, and terephthalic acid as main constituent units.

[0077] As the liquid crystal polyester, those comprising the following structural units (1), (2), and, if necessary, (3) and / or (4) are preferably used.

[0078] [ka]

[0079] [ka]

[0080] [ka]

[0081] [ka]

[0082] The structural units (1) and (2) are structural units of a polyester formed from p-hydroxybenzoic acid and 2-hydroxy-6-naphthoic acid, respectively.

[0083] The structural units (1) and (2) are preferred from the viewpoint of obtaining a resin having an excellent balance of mechanical properties such as heat resistance, fluidity, and rigidity.

[0084] The liquid crystal polyester is a polymer having the following structural unit (5): [ka] may include:

[0085] X in the structural units (3), (4) and (5) each independently represents -(CH2) n - (wherein n is an integer of 1 to 6), and the following structural group (6):

[0086] [ka] (wherein Y is halogen, alkyl or aryl). is a divalent group selected from the group consisting of:

[0087] The structural unit (3) is preferably a structural unit generated from one or more selected from ethylene glycol, hydroquinone, 4,4'-dihydroxybiphenyl, 2,6-dihydroxynaphthalene, bisphenol A, etc., more preferably a structural unit generated from one or more selected from ethylene glycol, 4,4'-dihydroxybiphenyl, and hydroquinone, and even more preferably a structural unit generated from one or more selected from ethylene glycol and 4,4'-dihydroxybiphenyl.

[0088] The structural unit (4) is preferably a structural unit generated from one or more selected from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, and the like, and more preferably a structural unit generated from one selected from 2,6-naphthalenedicarboxylic acid and terephthalic acid.

[0089] As each of the structural unit (3) and the structural unit (4), two or more of the above structural units may be used in combination. When two or more types are used in combination, for example, in the structural unit (3), combinations of a structural unit generated from ethylene glycol and a structural unit generated from hydroquinone, a structural unit generated from ethylene glycol and a structural unit generated from 4,4'-dihydroxybiphenyl, and a structural unit generated from hydroquinone and a structural unit generated from 4,4'-dihydroxybiphenyl can be mentioned. In addition, in the structural unit (4), combinations of a structural unit generated from terephthalic acid and a structural unit generated from isophthalic acid, and a structural unit generated from terephthalic acid and a structural unit generated from 2,6-naphthalenedicarboxylic acid can be mentioned.

[0090] The proportions of the structural units (1), (2), (3), and (4) used in the liquid crystal polyester are not particularly limited. However, it is preferred that the structural units (3) and (4) are used in approximately equimolar amounts, for example, that the ratio of the number of moles of the structural unit (4) to the number of moles of the structural unit (3) is 0.9 or more and 1.1 or less.

[0091] Examples of the structural unit (5) include combinations of a structural unit generated from ethylene glycol and a structural unit generated from terephthalic acid, a structural unit generated from hydroquinone and a structural unit generated from terephthalic acid, a structural unit generated from 4,4'-dihydroxybiphenyl and a structural unit generated from terephthalic acid, a structural unit generated from 4,4'-dihydroxybiphenyl and a structural unit generated from isophthalic acid, a structural unit generated from bisphenol A and a structural unit generated from terephthalic acid, and a structural unit generated from hydroquinone and 2,6-naphthalenedicarboxylic acid.

[0092] The liquid crystal polyester may further contain structural units derived from other aromatic dicarboxylic acids, aromatic diols, and / or aromatic hydroxycarboxylic acids, if necessary, in a small amount that does not impair the characteristics and effects of this embodiment.

[0093] The temperature at which the liquid crystal polyester begins to exhibit a liquid crystal state when melted (hereinafter referred to as liquid crystal onset temperature) is preferably 150 to 350° C., more preferably 180 to 320° C., from the viewpoint of a balance between color tone, heat resistance, and moldability. The liquid crystal onset temperature of the present disclosure is the temperature at which an anisotropic molten phase is observed under polarized light while the liquid crystal polyester is heated at a temperature increase rate of 1° C. / min using a polarizing microscope having a heating stage.

[0094] The dielectric loss tangent (tan δ) of the liquid crystal polyester at 25°C and 1 MHz is preferably 0.03 or less, more preferably 0.025 or less, from the viewpoint of reducing dielectric loss and suppressing electrical noise when the injection molded article of the present embodiment is used in an electronic / electronic component. In particular, the dielectric loss tangent (tan δ) at 25°C and in a high frequency range (1 to 10 GHz range in one embodiment) is preferably 0.03 or less, or 0.025 or less. The dielectric loss tangent of the present disclosure is a value determined by a test method in accordance with JIS-K6911.

[0095] The apparent melt viscosity of the liquid crystal polyester (liquid crystal onset temperature +30°C and shear rate 100 / sec) is preferably 10 to 3,000 Pa·s, more preferably 10 to 2,000 Pa·s, and even more preferably 10 to 1,000 Pa·s. By setting the apparent melt viscosity within this range, the fluidity of the resin can be made favorable. Specifically, the method for measuring the apparent melt viscosity in the present embodiment includes a method for measuring the viscosity at a shear rate using a capillary rheometer. The melt viscosity at 300°C and a shear rate of 100 sec-1 can be measured by a capillary rheometer, for example, using a Capillograph (manufactured by Toyo Seiki Seisakusho Co., Ltd.) with a capillary length of 10 mm and a capillary diameter of 1 mm, at a temperature of 300°C and a shear rate of 100 sec-1. -1 It can be measured at.

[0096] (polyamide) The polyamide is not particularly limited as long as it has an amide bond {-NH-C(=O)-} in the repeating structure of the polymer. The method for producing the polyamide is not particularly limited, but includes ring-opening polymerization of lactams, polycondensation of diamines and dicarboxylic acids, and polycondensation of aminocarboxylic acids.

[0097] The diamine may be an aliphatic diamine, an alicyclic diamine, or an aromatic diamine. Examples of the diamine include tetramethylenediamine, hexamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecamethylenediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 5-methylnonamethylenediamine, 1,3-bisaminomethylcyclohexane, 1,4-bisaminomethylcyclohexane, m-phenylenediamine, p-phenylenediamine, m-xylylenediamine, and p-xylylenediamine.

[0098] The dicarboxylic acid may be an aliphatic dicarboxylic acid, an alicyclic dicarboxylic acid, or an aromatic dicarboxylic acid, such as adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, 1,1,3-tridecanedioic acid, 1,3-cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, or dimer acid.

[0099] Examples of lactams include ε-caprolactam, enantholactam, and ω-laurolactam.

[0100] Examples of the aminocarboxylic acid include ε-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, and 13-aminotridecanoic acid.

[0101] The polyamide may be a copolymer polyamide obtained by polycondensation of lactams, diamines, dicarboxylic acids, and / or ω-aminocarboxylic acids, either alone or in a mixture of two or more of them. Also suitable for use is a copolymer polyamide obtained by polymerizing lactams, diamines, dicarboxylic acids, and / or ω-aminocarboxylic acids in a polymerization reactor to the stage of low molecular weight oligomers, and then increasing the molecular weight with an extruder or the like.

[0102] Suitable polyamides include polyamide 6, polyamide 66, polyamide 46, polyamide 11, polyamide 12, polyamide 610, polyamide 612, polyamide 6 / 66, polyamide 6 / 612, polyamide MXD (m-xylylenediamine) 6, polyamide 6T, polyamide 6I, polyamide 6 / 6T, polyamide 6 / 6I, polyamide 66 / 6T, polyamide 66 / 6I, polyamide 6T / 6I, polyamide 6 / 6T / 6I, polyamide 66 / 6T / 6I, polyamide 6 / 12 / 6T, polyamide 66 / 12 / 6T, polyamide 6 / 12 / 6I, polyamide 66 / 12 / 6I, and polyamide 9T. For example, polyamide 6I means a polymerized polyamide of hexamethylenediamine and isophthalic acid, and polyamide 6 / 6T means a copolymerized polyamide of ε-aminocaproic acid, hexamethylenediamine, and terephthalic acid. In addition, polyamides obtained by further copolymerizing two or more of these polyamides in an extruder or the like can also be used.

[0103] As the polyamide, a polyamide having an aromatic ring in the repeating structural unit is useful from the viewpoint of improving the heat resistance of the molded product.Specific examples of the polyamide include polyamide MXD (m-xylylenediamine) 6, polyamide 6T, polyamide 6I, polyamide 6 / 6T, polyamide 6 / 6I, polyamide 66 / 6T, polyamide 66 / 6I, polyamide 6T / 6I, polyamide 6 / 6T / 6I, polyamide 66 / 6T / 6I, polyamide 6 / 12 / 6T, polyamide 66 / 12 / 6T, polyamide 6 / 12 / 6I, polyamide 66 / 12 / 6I, and polyamide 9T, and more preferably polyamide 6T / 6I, polyamide 66 / 6T / 6I, and polyamide 9T, and further preferably polyamide 9T.A mixture of two or more kinds selected from the above polyamides is also preferable.

[0104] The viscosity of the polyamide is preferably 70 to 160 ml / g, or 80 to 150 ml / g, as measured in 96% sulfuric acid according to ISO307, from the viewpoint of suppressing leakage from the nozzle during molding and excessive shear heat generation.

[0105] The polyamide may be a mixture of two or more types of polyamides that are the same type but have different viscosity numbers. The combination of viscosity numbers may be determined as desired, and examples include a mixture of a polyamide with a viscosity number of 150 to 200 ml / g and a polyamide with a viscosity number of 50 to 100 ml / g, and a mixture of multiple polyamides with viscosity numbers in the range of 50 to 150 ml / g. The viscosity of the polyamide mixture is a value measured according to ISO307 by dissolving the polyamide mixture in 96% sulfuric acid.

[0106] The terminal amino group concentration of the polyamide may be, from the viewpoint of improving the compatibility of the polyamide with other resins and / or various fillers, preferably 5 μmol / g or more, or 10 μmol / g or more, or 12 μmol / g or more, or 15 μmol / g or more, and from the viewpoint of well controlling the injection moldability, is preferably 45 μmol / g or less, or 40 μmol / g or less, or 35 μmol / g or less, or 30 μmol / g or less.

[0107] From the viewpoint of obtaining a resin having excellent mechanical properties such as fluidity and rigidity, the terminal carboxyl group concentration of the polyamide is preferably 20 μmol / g or more, or 30 μmol / g or more, and preferably 150 μmol / g or less, or 100 μmol / g or less, or 80 μmol / g or less.

[0108] The ratio of the terminal amino group concentration to the terminal carboxyl group concentration of the polyamide (terminal amino group concentration / terminal carboxyl group concentration) is not particularly limited, but from the viewpoint of mechanical properties, it is preferably 1.0 or less, or 0.9 or less, or 0.8 or less, or 0.7 or less, and from the viewpoint of stabilizing compatibility with other materials, it is preferably 0.1 or more.

[0109] The terminal amino group concentration and terminal carboxyl group concentration of the polyamide can be adjusted by a known method, and examples of such methods include adding a terminal regulator such as a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacid halide, a monoester, or a monoalcohol so as to achieve a predetermined terminal concentration during polymerization of the polyamide.

[0110] Examples of the terminal conditioner that reacts with the terminal amino group include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of two or more of these. As these monocarboxylic acid compounds, from the standpoints of reactivity, stability of the blocked terminal, cost, etc., acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred, and benzoic acid is more preferred.

[0111] Examples of the terminal regulator that reacts with the terminal carboxyl group include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine; and mixtures of two or more of these. As these monoamine compounds, butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred in terms of reactivity, boiling point, stability of the blocked terminal, price, etc.

[0112] The concentration of terminal amino groups and terminal carboxyl groups of the polyamide is 1 From the viewpoints of accuracy and simplicity, it is preferable to determine the value from the integral of the characteristic signal corresponding to each terminal group by H-NMR, and for example, the method disclosed in JP-A-7-228775 can be followed. Deuterated trifluoroacetic acid is preferably used as the measurement solvent. 1 The number of 1 H-NMR scans is preferably at least 300, even when the measurement is performed using an instrument with sufficient resolution.

[0113] The concentrations of terminal amino groups and terminal carboxyl groups of a polyamide can also be measured by a titration method such as that disclosed in JP-A-2003-055549.

[0114] From the viewpoint of eliminating the influence of additives, lubricants, etc., 1 Quantitation by H-NMR is more preferred.

[0115] When the terminal amino group and / or terminal carboxyl group are adjusted using a terminal blocking agent, the active terminal is blocked. When, for example, benzoic acid, which is a monocarboxylic acid, is used as the terminal blocking agent, the terminal group blocked at the phenyl group end is generated. The concentration of blocked terminal groups of the polyamide is preferably 20% or more, more preferably 40% or more, even more preferably 45% or more, even more preferably 50% or more, and preferably 85% or less, more preferably 80% or less, and even more preferably 75% on a molar basis.

[0116] The terminal capping rate of the polyamide can be calculated by measuring the number of terminal carboxyl groups, terminal amino groups, and terminal groups capped with a terminal capping agent present in the polyamide, and calculating according to the following formula. End sealing rate (%)=[(α-β) / α]×100 (wherein α represents the total number of terminal groups in the molecular chain (which is usually equal to twice the number of polyamide molecules), and β represents the total number of terminal carboxyl groups and terminal amino groups that remain uncapped.)

[0117] The water content of the polyamide is preferably in the range of 500 to 3000 mass ppm, more preferably in the range of 500 to 2000 mass ppm. By making the water content of the polyamide 500 mass ppm or more, pellets with good color tone can be obtained, and by making it 3000 mass ppm or less, a significant decrease in viscosity of the resin can be suppressed. The water content is a value measured by a moisture evaporation method in accordance with ISO15512 Method B.

[0118] (Polyphenylene ether) In the present embodiment, the polyphenylene ether is represented by the following general formula (7): [ka] (In the formula, R1 to R4 each independently represent a hydrogen atom, a halogen atom, a primary or secondary C1 to C7 alkyl group, a phenyl group, a C1 to C7 haloalkyl group, a C1 to C7 aminoalkyl group, a C1 to C7 hydrocarbyloxy group, or a halohydrocarbyloxy group (with the proviso that at least two carbon atoms separate the halogen atom from the oxygen atom).) It is a homopolymer and / or copolymer having a repeating structural unit represented by the following formula:

[0119] The method for producing polyphenylene ether is not particularly limited as long as it is a known method, and examples thereof include the methods described in U.S. Pat. No. 3,306,874, U.S. Pat. No. 3,306,875, U.S. Pat. No. 3,257,357, U.S. Pat. No. 3,257,358, JP-A-50-51197, JP-B-52-17880, and JP-B-63-152628.

[0120] Examples of polyphenylene ethers include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), and the like.

[0121] Examples of polyphenylene ether copolymers include copolymers of 2,6-dimethylphenol with other phenols, such as copolymers with 2,3,6-trimethylphenol and copolymers with 2-methyl-6-butylphenol.

[0122] As the polyphenylene ether, from the viewpoint of commercial availability, poly(2,6-dimethyl-1,4-phenylene ether), a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, or a mixture thereof is preferred. When a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol is used, the ratio of each monomer unit in the polyphenylene ether copolymer is preferably 10 to 30 mass%, or 15 to 25 mass%, or 20 to 25 mass%.

[0123] The reduced viscosity (ηsp / c: dl / g, 0.5 g / dl chloroform solution, measured at 30°C) of the polyphenylene ether is preferably 0.30 dl / g or more from the viewpoint of mechanical strength, and is preferably 0.55 dl / g or less, or 0.53 dl / g or less, or 0.45 dl / g or less, or 0.36 dl / g or less from the viewpoint of improving compatibility with other materials.

[0124] The polyphenylene ether may be a mixture of two or more different types of polyphenylene ethers having different reduced viscosities. For example, a mixture of a polyphenylene ether having a reduced viscosity of about 0.40 dl / g and a polyphenylene ether having a reduced viscosity of about 0.50 dl / g, a mixture of a low molecular weight polyphenylene ether having a reduced viscosity of about 0.08 to 0.12 dl / g and a polyphenylene ether having a reduced viscosity of about 0.50 dl / g, etc. The reduced viscosity of the mixture of two or more types of polyphenylene ethers having different reduced viscosities is preferably in the range of 0.30 to 0.55 dl / g.

[0125] The polyphenylene ether may be modified with a modifying agent. Examples of the modifying agent include saturated or unsaturated dicarboxylic acids and derivatives thereof, such as maleic anhydride, N-phenylmaleimide, malic acid, citric acid, and fumaric acid, and vinyl compounds, such as styrene, acrylic acid esters, and methacrylic acid esters. The polyphenylene ether may be modified in advance, or may be modified simultaneously with extrusion by adding a modifying agent when the resin is melt-extruded.

[0126] (Polyarylene sulfide) Polyarylene sulfide has the following general formula: [-Ar-S-] (In the formula, Ar represents a divalent group containing an arylene structure.) The polymer may contain 50 mol % or more, 70 mol % or more, or 90 mol % or more of arylene sulfide units represented by the following formula: Ar may be a p-phenylene group, an m-phenylene group, a substituted phenylene group, a p,p'-diphenylenesulfone group, a p,p'-biphenylene group, a p,p'-diphenylenecarbonyl group, a naphthylene group, or the like. The arylene structure may be a substituted arylene. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, and a phenyl group.

[0127] The polyarylene sulfide may be a homopolymer having one type of arylene group as a structural unit, or may be a copolymer obtained by mixing two or more different arylene groups from the viewpoint of processability and heat resistance. As the polyarylene sulfide, polyphenylene sulfide having phenylene groups as the arylene group is preferable, and polyphenylene sulfide having a repeating unit of p-phenylene sulfide as the main structural element (hereinafter, sometimes simply abbreviated as "PPS") is more preferable because it has excellent processability and heat resistance and is easily available industrially.

[0128] After the linear PPS is polymerized, it is further heated in the presence of oxygen at a temperature below the melting point of PPS (for example, 200 to 250°C) to promote oxidative crosslinking and appropriately increase the polymer molecular weight or viscosity to obtain a crosslinked PPS. Crosslinked PPS also includes semi-crosslinked PPS in which the degree of crosslinking is kept to a minimum.

[0129] The PPS may be a combination of one or two of linear PPS and crosslinked PPS. The combination of linear PPS and crosslinked PPS is preferred from the viewpoint of the balance between fluidity and toughness.

[0130] Shear rate of polyarylene sulfide: 100 sec -1 The melt viscosity at 300°C in the above-mentioned composition is preferably 10 Pa·s or more from the viewpoint of imparting excellent mechanical properties to the resin, and is preferably 150 Pa·s or less, or 100 Pa·s or less, or 80 Pa·s or less from the viewpoint of obtaining good injection moldability. The above melt viscosity is a value measured by a capillary rheometer, and is measured, for example, by using a Capillograph (manufactured by Toyo Seiki Seisakusho Co., Ltd.) with a capillary length of 10 mm and a capillary diameter of 1 mm at a temperature of 300°C and a shear rate of 100 sec -1 It can be measured at.

[0131] (Polyarylate) Polyarylates are polymers containing aromatic rings and ester bonds in their structural units, and are also called polyaryl esters. Examples of polyarylates include those represented by the following formula (8): [ka] Preferably used is a polyarylate having a repeating unit represented by the following formula: A polyarylate having a molar ratio of terephthalic acid to isophthalic acid of about 1:1 is preferred from the viewpoints of heat resistance in a molded product and toughness of the resin.

[0132] As the polyarylate, commercially available products may be used, for example, "U Polymer" manufactured by Unitika Ltd.

[0133] The molecular weight of the polyarylate is preferably a number average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC) of 5000 to 300000, more preferably 10000 to 300000, and even more preferably 10000 to 100000. When the number average molecular weight of the polyarylate is 5000 or more, the heat resistance of the molded article tends to be good and the mechanical strength of the resin tends to be high, and when it is 300000 or less, the fluidity of the resin tends to be good.

[0134] Specifically, the number average molecular weight in terms of polystyrene is determined from a detection time-molecular weight curve of a standard polystyrene previously measured under the same conditions using GPC, chloroform as a solvent, and a column temperature of 40° C. In this case, the concentration of the polyarylate in the chloroform solution is 1 g / L. In addition, it is preferable to use an ultraviolet absorption detector at about 280 nm for the measurement.

[0135] (Polyethersulfone, polyetherimide, polysulfone) The polyethersulfone, polyetherimide, and polysulfone can be appropriately selected from among known amorphous super engineering plastics.

[0136] Examples of commercially available polyethersulfone products include Radel A (registered trademark) and Radel R (registered trademark) manufactured by Solvay Advanced Polymers, MITSUI PES manufactured by Mitsui Chemicals, Inc., and Ultrason E (registered trademark) manufactured by BASF Japan Ltd.

[0137] Commercially available polyetherimides include, for example, Ultem (registered trademark) manufactured by SABIC Innovative Plastics.

[0138] Examples of commercially available polysulfone products include Udel (registered trademark) and Mindel (registered trademark) manufactured by Solvay Advanced Polymers, and Ultrason S (registered trademark) manufactured by BASF Japan.

[0139] (Polyarylketone) Polyaryl ketone is a thermoplastic resin containing an aromatic ring, an ether bond, and a ketone bond in its structural unit, and examples thereof include polyether ketone, polyether ether ketone, and polyether ketone ketone. [ka] Preferred is a polyether ether ketone having a repeating unit represented by the following formula:

[0140] As the polyether ether ketone, commercially available products may be used, for example, products manufactured by VICTREX under the trade names "PEEK151G", "PEEK90G", "PEEK381G", "PEEK450G", and "PEK" (registered trademark), products manufactured by BASF under the trade name "Ultrapek" (PEKEKK) (registered trademark), etc., and the product manufactured by VICTREX under the trade name "PEEK" (registered trademark) is preferably used. The polyaryl ketones may be used alone or in combination of two or more kinds.

[0141] The molecular weight of the polyaryl ketone can be indicated by its melt viscosity. The melt viscosity is preferably 50 Pa·s or more, or 70 Pa·s or more, or 100 Pa·s or more in terms of good mechanical strength of the resin, and is preferably 5000 Pa·s or less, or 3000 Pa·s or less, or 2500 Pa·s or less, or 1000 Pa·s or less in terms of good moldability of the resin. The melt viscosity of the polyaryl ketone is the apparent melt viscosity measured when the polyaryl ketone heated to 400°C is extruded from a nozzle having an inner diameter of 1 mm and a length of 10 mm under a load of 100 kg.

[0142] (Polyacetal) The polyacetal includes polyacetal homopolymer and polyacetal copolymer, and known polyacetal may be used.

[0143] Polyacetal homopolymers are obtained by homopolymerizing formaldehyde monomers or cyclic oligomers of formaldehyde such as its trimer (trioxane) and tetramer (tetraoxane), and therefore are substantially composed of oxymethylene units.

[0144] The polyacetal copolymer is obtained by copolymerizing a formaldehyde monomer or a cyclic oligomer of formaldehyde such as its trimer (trioxane) and tetramer (tetraoxane) with a glycol (ethylene oxide, propylene oxide, etc.), a cyclic ether (epichlorohydrin, 1,3-dioxolane, etc.), or a cyclic formal (1,4-butanediol formal, etc.). Examples of the polyacetal copolymer include a branched polyacetal copolymer obtained by copolymerizing a formaldehyde monomer and / or a cyclic oligomer with a monofunctional glycidyl ether, and a crosslinked polyacetal copolymer obtained by copolymerizing a formaldehyde monomer and / or a cyclic oligomer with a polyfunctional glycidyl ether.

[0145] The polyacetal may have a functional group such as a hydroxyl group at both ends or one end. For example, it may be a polyacetal homopolymer having a block component obtained by polymerizing a formaldehyde monomer or a cyclic oligomer in the presence of a polyalkylene glycol.

[0146] The polyacetal may be a polyacetal copolymer having a block component obtained by copolymerizing a formaldehyde monomer or a cyclic oligomer of formaldehyde, such as its trimer (trioxane) and tetramer (tetraoxane), with a cyclic ether or a cyclic formal in the presence of a compound having a functional group such as a hydroxyl group at both ends or one end (for example, hydrogenated polybutadiene glycol).

[0147] The polyacetal may be used alone or in a mixture of two or more. From the viewpoint of thermal stability, the mixture preferably contains 50% by mass or more, or 80% by mass or more, or 95% by mass or more of the polyacetal copolymer.

[0148] The polyacetal copolymer can be obtained, for example, by the following method. For example, when a polyacetal copolymer is obtained using trioxane, the comonomer such as the above-mentioned 1,3-dioxolane is generally used in an amount of 0.1 to 60 mol%, preferably 0.1 to 20 mol%, and more preferably 0.13 to 10 mol% relative to 100 mol% of trioxane. The preferred melting point of the polyacetal copolymer is 162°C to 173°C, more preferably 167°C to 173°C, and even more preferably 167°C to 171°C. For example, a polyacetal copolymer having a melting point of 167°C to 171°C can be obtained by using about 1.3 to 3.5 mol% of the comonomer relative to 100 mol% of trioxane. The comonomer is polymerized by a known method in the presence of a known polymerization catalyst, a polymerization chain agent (chain transfer agent), and the like, to obtain the desired polyacetal copolymer.

[0149] (Thermoplastic elastomer) The thermoplastic elastomer may be at least one selected from the group consisting of an olefin resin, a block copolymer of an aromatic vinyl compound and a conjugated diene compound, and a partially hydrogenated product of a block copolymer of an aromatic vinyl compound and a conjugated diene compound.

[0150] Examples of olefin resins include polyethylene (high density polyethylene, medium density polyethylene, high pressure low density polyethylene, linear low density polyethylene, and very low density polyethylene), polypropylene, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-octene copolymers, polypropylene-butene copolymers, polybutene, hydrogenated polybutadiene, ethylene-acrylate copolymers, ethylene-methacrylate copolymers, ethylene-acrylic acid copolymers, and ethylene-vinyl acetate copolymers.

[0151] The olefin resin may be a modified product. Examples of the modified product include a graft copolymer in which one or more vinyl compounds different from the monomer constituting the olefin resin are grafted; a modified product with an α,β-unsaturated carboxylic acid (acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, nadic acid, etc.) or an acid anhydride thereof (in combination with a peroxide if necessary); and a copolymer of a monomer constituting the olefin resin and an acid anhydride.

[0152] As the block copolymer of an aromatic vinyl compound and a conjugated diene compound, a block copolymer having one or more bonding patterns selected from an AB type, an ABA type, and an ABAB type, which is composed of an aromatic vinyl compound block and a conjugated diene compound block, is preferred.

[0153] The partially hydrogenated product of the block copolymer of an aromatic vinyl compound and a conjugated diene compound refers to a block copolymer of the aromatic vinyl compound and a conjugated diene compound that is hydrogenated to control the hydrogenation rate of the aliphatic double bonds in the block copolymer to a range of more than 0% and less than 100%. The hydrogenation rate of the partially hydrogenated block copolymer is preferably 50% or more, more preferably 80% or more, and most preferably 98% or more.

[0154] The term "aromatic vinyl compound block" as used herein refers to a polymer block mainly made of an aromatic vinyl compound, and the term "conjugated diene compound block" as used herein refers to a polymer block mainly made of a conjugated diene compound. In this case, "mainly made" refers to a polymer block mainly made of a conjugated diene compound that comprises at least 50% by mass, and more preferably 80% by mass or more.

[0155] Specific examples of the aromatic vinyl compound constituting the aromatic vinyl compound block include styrene, α-methylstyrene, vinyltoluene, etc., and one or more compounds selected from these are used. Among these, styrene is particularly preferred.

[0156] Specific examples of the conjugated diene compound constituting the conjugated diene compound block include butadiene, isoprene, piperylene, 1,3-pentadiene, etc., and one or more compounds selected from these are used. Among these, butadiene, isoprene, and combinations thereof are preferred.

[0157] The microstructure of the conjugated diene compound block portion of the block copolymer preferably has a 1,2-vinyl content or a total content of the 1,2-vinyl content and the 3,4-vinyl content of 5 to 80%, more preferably 10 to 50%, and most preferably 15 to 40%.

[0158] The mass ratio of the aromatic vinyl compound to the conjugated diene compound in the block copolymer is preferably 10 / 90 to 90 / 10, or 15 / 85 to 80 / 20, or 15 / 85 to 65 / 35, or 20 / 80 to 45 / 55.

[0159] The number average molecular weight of the block copolymer is measured by gel permeation chromatography at 40° C. using chloroform as a solvent and converted into standard polystyrene, and is preferably 10,000 to 500,000, more preferably 200,000 to 300,000, and most preferably 200,000 to 250,000.

[0160] The number average molecular weight of one aromatic vinyl compound block in the block copolymer is more preferably 20,000 or more.

[0161] The number average molecular weight of one aromatic vinyl compound block in the block copolymer referred to here can be calculated by the following formula using the number average molecular weight of the partially hydrogenated block copolymer measured by the above-mentioned method. Mn(a) = {Mn×a / (a+b)} / N [In the above formula, Mn(a) represents the number average molecular weight of one aromatic vinyl compound block, Mn represents the number average molecular weight of the block copolymer, a represents the mass % of all aromatic vinyl compound blocks in the block copolymer, b represents the mass % of all conjugated diene compound blocks in the block copolymer, and N represents the number of aromatic vinyl compound blocks in the block copolymer.]

[0162] The block copolymer may be used by mixing two or more types of copolymers having different bond types, different number average molecular weights, different aromatic vinyl compound types, different conjugated diene compound types, different 1,2-vinyl contents or the total amount of 1,2-vinyl content and 3,4-vinyl content, different aromatic vinyl compound component contents, different hydrogenation rates, etc. Among these mixed types, it is preferable to mix two or more types of copolymers having different number average molecular weights.

[0163] Furthermore, the block copolymer may be a blend of two or more types of copolymers having different mass ratios of the aromatic vinyl compound and the conjugated diene compound.

[0164] The block copolymer may be modified. Examples of the modified product include those modified with α,β-unsaturated carboxylic acid (acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, nadic acid, etc.) or an acid anhydride thereof, optionally with a peroxide. The preferred modification rate is 0.1 to 5% by mass. The modification rate can be determined, for example, by preparing a calibration curve by infrared spectroscopy using a sample previously mixed with a modifying agent, dissolving the sample in a soluble solvent and reprecipitating it, and measuring the sample from which the unreacted modifying agent has been removed.

[0165] <Filler> The filler that may be contained in the first component and / or the second component may be an organic filler and / or an inorganic filler. Organic fillers are preferred because of their low specific gravity. Examples of organic fillers include cellulose (e.g., cellulose nanofibers, cellulose whiskers, cellulose microfibers, etc.), organic-containing carbon fillers (carbon black, carbon fibers, etc.), and various synthetic polymers. Among these, the nozzle shape of the present embodiment is useful for organic fillers that are difficult to finely disperse, such as cellulose nanofibers and carbon black.

[0166] Among various additives, compatibilizers are useful for changing the dispersion state. For example, when the resin is a polymer alloy of polyamide and polyphenylene ether, or a polymer alloy of polyamide and polypropylene, organic acids such as maleic anhydride, citric acid, and fumaric acid are useful as compatibilizers. When the resin is an alloy of polyphenylene sulfide and polyphenylene ether, thermoplastic resins having glycidyl groups and epoxy compounds are useful.

[0167] As an additive, a plasticizer is also useful. The plasticizer can improve moldability by reducing the melt viscosity of the resin. As the plasticizer, an ester consisting of an acid component and an alcohol component is useful. Examples of the ester include phthalate compounds such as dioctyl phthalate, diisononyl phthalate, diisodecyl phthalate, and dibutyl phthalate, adipic acid ester compounds such as dioctyl adipate and diisononyl adipate, trimellitic acid ester compounds such as trioctyl trimellitate, citrate compounds, sebacic acid ester compounds, azelaic acid ester compounds, benzoic acid ester compounds, low molecular weight polyesters, phosphate compounds such as tricresyl phosphate, triphenyl phosphate, and bisphenol A-bis(diphenyl phosphate), and modified vegetable oils such as epoxidized vegetable oils.

[0168] (Cellulose nanofiber) The cellulose nanofibers as a filler that may be contained in the first component and / or the second component may be obtained from various cellulose fiber raw materials selected from natural cellulose and regenerated cellulose. In one embodiment, the cellulose fiber raw material may be chemically modified. The cellulose nanofibers can be obtained by beating and fibrillating the cellulose fiber raw material by mechanical force such as a beater or refiner, and then defibrating the cellulose fiber raw material by a pulverizing method such as a high-pressure homogenizer, microfluidizer, ball mill, disk mill, mixer (e.g., homomixer), etc.

[0169] The number average fiber diameter of the cellulose nanofibers is, in one aspect, 2 nm or more, preferably 4 nm or more, more preferably 10 nm or more, even more preferably 20 nm or more, and particularly preferably 30 nm or more, in that the crystallinity of cellulose is well maintained. On the other hand, the upper limit is, in one aspect, less than 1000 nm, preferably 800 nm or less, more preferably 500 nm or less, and even more preferably 300 nm or less, in that the effect as a filler is good.

[0170] From the viewpoint of satisfactorily improving the mechanical properties of an injection-molded article containing cellulose nanofibers with a small amount of cellulose nanofibers, the number average fiber length / number average fiber diameter (L / D) of the cellulose nanofibers is preferably 50 or more, or 80 or more, or 100 or more, or 120 or more, or 150 or more. There is no particular upper limit, but from the viewpoint of handleability, it is preferably 5,000 or less.

[0171] In the present disclosure, the number average fiber diameter, number average fiber length, and L / D ratio of cellulose nanofibers are obtained by diluting an aqueous dispersion of cellulose nanofibers with a water-soluble solvent (e.g., water, ethanol, tert-butanol, etc.) to 0.001 to 0.1% by mass, dispersing the cellulose nanofibers using a high-shear homogenizer (e.g., IKA, product name "Ultra Turrax T18") under processing conditions: rotation speed 25,000 rpm x 5 minutes, casting the homogenized cellulose nanofibers on a hydrophilic substrate (e.g., mica), and air-drying the resulting sample, which is then measured with a high-resolution scanning electron microscope (SEM) or atomic force microscope (AFM). Specifically, the length (L) and diameter (D) of 100 randomly selected fibrous substances are measured in an observation field where the magnification is adjusted so that at least 100 fibrous substances are observed, and the ratio (L / D) is calculated. The number average value of the length (L), the number average value of the diameter (D), and the number average value of the ratio (L / D) of the cellulose nanofibers are calculated.

[0172] In a typical embodiment, the crystal structure of the cellulose nanofiber has cellulose type I and / or type II. Known crystal forms of cellulose include type I, type II, type III, and type IV. Type I and type II cellulose are widely used, while type III and type IV cellulose are not widely used on an industrial scale, although they have been obtained on a laboratory scale.

[0173] The crystal structure can be identified from the diffraction profile obtained by wide-angle X-ray diffraction using CuKα (λ=0.15418 nm) monochromated with graphite. Cellulose type I has two peaks at 2θ=14-17° and 2θ=22-23°. Cellulose type II has one peak at 2θ=10°-19° and two peaks at 2θ=19°-25°. When cellulose type I and cellulose type II are mixed, a maximum of six peaks are observed in the range of 2θ=10°-25°.

[0174] From the viewpoint of obtaining good mechanical properties, the crystallinity of the cellulose nanofiber of this embodiment is preferably 50% or more, more preferably 60% or more, even more preferably 65% ​​or more, and most preferably 70% or more. Since a higher crystallinity of the cellulose nanofiber tends to be more preferable, there is no particular upper limit, but from the viewpoint of production, a preferred upper limit is 99%.

[0175] When the cellulose nanofiber is cellulose type I crystal (derived from natural cellulose), the degree of crystallinity can be calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring the sample by wide-angle X-ray diffraction using the Segal method, according to the following formula:

[0176] Crystallinity (%)=[I (200) -I (amorphous) ] / I (200) ×100 I (200) : Diffraction peak intensity due to 200 plane (2θ=22.5°) in cellulose I crystal I (amorphous) : The halo peak intensity due to the amorphous phase in cellulose I crystals, which is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200 plane (2θ=18.0°)

[0177] Furthermore, when the cellulose nanofiber is a cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%)=h1 / h0×100

[0178] The degree of polymerization (DP) of the cellulose nanofiber is preferably 100 or more, more preferably 150 or more, in terms of good tensile strength at break and elastic modulus, and from the viewpoint of easy availability, is preferably 12000 or less, more preferably 8000 or less. The degree of polymerization is determined as the degree of polymerization DP by determining the intrinsic viscosity (JIS P 8215:1998) of a dilute cellulose solution using a copper ethylenediamine solution, and then utilizing the relationship between the intrinsic viscosity of cellulose and the degree of polymerization DP expressed by the following formula:

[0179] Intrinsic viscosity [η]=K×DPa Here, K and a are constants determined by the type of polymer. In the case of cellulose, K is 5.7×10 -3 , a is 1.

[0180] The weight average molecular weight (Mw) of the cellulose nanofiber is preferably 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) of the cellulose nanofiber is preferably 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecules are the starting points of thermal decomposition, when the cellulose nanofibers have not only a large weight average molecular weight but also a narrow molecular weight distribution width, a cellulose nanofiber with particularly high heat resistance can be obtained. The weight average molecular weight (Mw) of the cellulose fiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of the cellulose raw material. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more, from the viewpoint of ease of production of cellulose fibers. Mw can be controlled within the above range by selecting a cellulose raw material having an Mw appropriate for the purpose, performing physical and / or chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. Mw / Mn can also be controlled within the above range by selecting a cellulose raw material having an Mw / Mn appropriate for the purpose, performing physical and / or chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include dry or wet grinding using a microfluidizer, ball mill, disk mill, etc., physical treatment that applies mechanical forces such as impact, shear, shear, and friction using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, etc., and examples of the chemical treatment include digestion, bleaching, acid treatment, and regenerated cellulose.

[0181] Here, the weight average molecular weight and number average molecular weight of the cellulose nanofiber are values ​​obtained by dissolving the cellulose nanofiber in N,N-dimethylacetamide containing added lithium chloride and then performing gel permeation chromatography using N,N-dimethylacetamide as a solvent.

[0182] The cellulose nanofiber may be a chemically modified cellulose nanofiber that has been chemically modified with a modifying agent. The modifying agent may be a compound that reacts with the hydroxyl group of cellulose, and examples of the modifying agent include an esterifying agent, an etherifying agent, a silylating agent, and an isocyanate. In a preferred embodiment, the chemical modification is acylation using an esterifying agent. The esterifying agent may be a compound that reacts with the hydroxyl group of cellulose to produce an acyl group, such as a compound selected from a carboxylic acid halide, an acid anhydride (i.e., a carboxylic acid anhydride), a carboxylic acid vinyl ester, or a carboxylic acid. In a preferred embodiment, the esterification is acetylation.

[0183] The degree of modification of chemically modified cellulose nanofibers is expressed as the average degree of substitution of hydroxyl groups (the average number of hydroxyl groups substituted per glucose, which is the basic structural unit of cellulose, also referred to as DS). In one embodiment, DS is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.2 or more, and most preferably 0.3 or more, in terms of obtaining a high thermal decomposition onset temperature, and is preferably 2.0 or less, more preferably 1.8 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less, in terms of obtaining good tensile strength, dimensional stability, and thermal decomposition temperature due to the remaining unmodified cellulose skeleton.

[0184] The degree of acyl substitution (DS) of the esterified cellulose nanofiber can be calculated from the reflection infrared absorption spectrum of the esterified cellulose nanofiber based on the peak intensity ratio between the peak derived from the acyl group and the peak derived from the cellulose skeleton. The peak of the absorption band of C=O based on the acyl group is at 1730 cm -1The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose nanofibers was calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurements of esterified cellulose nanofibers (described below) and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on acyl groups to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using

[0185] The method for calculating the DS of esterified cellulose nanofibers using solid-state NMR is as follows: 13 C solid-state NMR measurement was performed, and the intensity can be calculated using the area intensity (Inf) of a signal assigned to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of signals assigned to carbons C1-C6 derived from the pyranose ring of cellulose, which appear in the range from 50 ppm to 110 ppm, using the following formula. DS = (Inf) x 6 / (Inp) For example, when the modifying group is an acetyl group, the signal at 23 ppm assigned to -CH3 may be used.

[0186] Use 13 The conditions for the C solid-state NMR measurement are, for example, as follows: Equipment:Bruker Biospin Avance500WB Frequency: 125.77MHz Measurement method: DD / MAS method Waiting time: 75sec NMR sample tube: 4mmφ Accumulation times: 640 times (approx. 14 hours) MAS: 14,500Hz Chemical shift reference: glycine (external reference: 176.03 ppm)

[0187] <Carbon black> Carbon black as a filler that may be contained in the first component and / or the second component may be used either simply for uniform coloring or for the purpose of imparting electrical conductivity.

[0188] The method for producing carbon black is not particularly limited, and any of the following methods may be used: oil furnace method, lamp black method, channel method, gas furnace method, acetylene decomposition method, thermal method, etc.

[0189] In a preferred embodiment, the dibutyl phthalate (DBP) oil absorption of the carbon black is 50 mL / 100 g or more and 600 mL / 100 g or less. From the viewpoint of imparting a function such as electrical conductivity, the DBP oil absorption is preferably 100 mL / 100 g or more, or 150 mL / 100 g or more, or 200 mL / 100 g or more, or 300 mL / 100 g or more. From the viewpoint of imparting uniform colorability, the DBP oil absorption is preferably 70 mL / 100 g or more, or 80 mL / 100 g or more, or 100 mL / 100 g or more, or 120 mL / 100 g or more. From the viewpoint of suppressing deterioration of fluidity, the DBP oil absorption is preferably 500 mL / 100 g or less, or 400 mL / 100 g or less, or 350 mL / 100 g or less, or 300 mL / 100 g or less. From the viewpoint of maintaining electrical conductivity while suppressing deterioration of fluidity, the oil absorption is preferably 550 mL / 100 g or less, 530 mL / 100 g or less, 510 mL / 100 g or less, or 500 mL / 100 g or less. The dibutyl phthalate oil absorption is disclosed in the catalogs of each carbon black manufacturer.

[0190] Coloring or imparting conductivity by carbon black is often insufficient by mixing in a molding machine alone, and generally, in order to increase reliability, a method is adopted in which raw material pellets melt-kneaded in an extruder are used to mold the product. By using the nozzle of this embodiment, it is possible to significantly reduce the formation of agglomerates in the carbon black molded product. There are various methods for confirming the reduction in agglomerates, but the following is an example of a preferred method.

[0191] The size and abundance ratio of carbon black aggregates are measured by the method described below. Specifically, a reflective optical microscope (e.g., PME3: manufactured by Olympus Corporation) is used to observe the dispersion state of carbon black on the smooth surface of the observation sample at a magnification of 100 times, and a photograph is taken. The photographed reflective micrograph is converted into a digital image (capture resolution: 400 dpi) by a scanner (e.g., CC-600PX: manufactured by Epson Corporation), and the number of black phases (secondary aggregates of carbon black) observed within the field of view of the obtained digital image is automatically measured and counted using image processing software. Using the above method, the number of black aggregates in the field of view was calculated, and 10 photographs (total field of view 10 mm) were 2 ) to calculate the average value.

[0192] Examples of inorganic fillers that may be contained in the first component and / or the second component include glass fiber, zeolite, ceramics, talc, mica, titanium dioxide, silica, wollastonite, dragonite, calcium carbonate, metal powder, etc. Among these, the nozzle shape of the present embodiment is particularly useful for inorganic fillers such as glass fiber and wollastonite, which, when blended at a high concentration, increase the viscosity of the resin and make dilution and dispersion difficult.

[0193] <Glass fiber> As the glass fiber, any glass fiber in a fibrous form can be used without any problem. Specific examples include chopped strand glass fiber, milled glass fiber, and glass fiber roving. Among these, chopped strand glass fiber and milled glass fiber are preferred from the viewpoint of handling, and chopped strand glass fiber is more preferred for increasing the strength of the resin molded body. These glass fibers may be used alone or in combination of two or more.

[0194] The preferred average fiber diameter of the glass fiber is 7 μm or more and 20 μm or less. From the viewpoint of fluidity, 8 μm or more, 9 μm or more, or 10 μm or more are preferred, and from the viewpoint of preventing scraping of the mold surface during molding, 18 μm or less, 15 μm or less, or 14 μm or less are preferred. The above average fiber diameter is a value measured by incinerating the measurement object at a temperature of about 650° C., removing the resin component, observing the obtained ash with a scanning electron microscope, and measuring the diameter. At this time, in order to eliminate errors, it is desirable to measure the diameters of at least 100 glass fibers and calculate the number average fiber diameter. When two or more types of glass fibers having different glass fiber diameters are blended, it is preferable that the number average fiber diameter is within the above range.

[0195] The number average fiber length of the glass fibers is preferably in the range of 150 μm or more and 350 μm or less. From the viewpoint of maintaining physical properties, it is preferably 160 μm or more, 170 μm or more, 180 μm or more, 190 μm or more, or 200 μm or more, and from the viewpoint of suppressing deterioration of fluidity, it is preferably 340 μm or less, 320 μm or less, 300 μm or less, or 290 μm or less.

[0196] The number-average fiber length is obtained by incinerating the object to be measured at a temperature of 500°C or less for 5 hours or more, and then slowly cooling the ash obtained. It is preferable to heat the object at a low temperature for a long time and then slowly cool the glass fibers, since this prevents the glass fibers from breaking due to thermal shock. The length of at least 1,000 glass fibers is measured for the obtained ash using a dynamic powder image analyzer (e.g., PITA-3 manufactured by Seishin Enterprise Co., Ltd.) and using soapy water containing a small amount of neutral detergent as a developing solvent. When measuring using a dynamic powder image analyzer, information corresponding to the glass fiber diameter is obtained as the minor axis of a circumscribed rectangle, and information corresponding to the glass fiber length is obtained as the major axis of a circumscribed rectangle. In order to eliminate measurement errors due to overlapping of multiple glass fibers, information on diameters that deviate by 2 μm or more from the glass fiber diameter confirmed by a scanning electron microscope, etc. is deleted. Specifically, when the glass fiber diameter confirmed by a scanning electron microscope or the like is 10 μm, information on particles with a circumscribed rectangle minor axis of 8 μm or less and information on particles with a circumscribed rectangle minor axis of 12 μm or more are deleted, and the number of remaining particles is calculated using information on 1,000 or more particles.

[0197] <Wollastonite> In this embodiment, wollastonite can be used as the inorganic filler. The preferred wollastonite has an average particle size in the range of 2 to 9 μm and an aspect ratio of 5 or more. The average particle size is the diameter of a sphere measured and calculated using a particle size analyzer (e.g., Sedigraph particle size analyzer (Model 5100, manufactured by Micromeritics Instrument, USA)) after adding 0.75 g of wollastonite particles to 45 ml of 0.05% Calgon solution and dispersing thoroughly in an ultrasonic bath. The aspect ratio is a value calculated from the arithmetic mean value of the diameters and lengths of at least 5,000 wollastonite particles measured using a photograph taken by observation with a scanning electron microscope. Two or more types of wollastonite particles having different aspect ratios may be used in combination.

[0198] For example, when a master batch containing a high concentration of wollastonite is diluted and molded using a general injection molding machine, poorly dispersed wollastonite aggregates can be confirmed as mottled white dots on the surface of the molded piece. Therefore, the initial evaluation of the dispersion state of wollastonite is possible based on the presence or absence of these aggregates.

[0199] <Nozzle and injection unit with nozzle> Another aspect of the present invention provides a capillary nozzle as described above in the section <Nozzle>, and a nozzle-equipped injection unit including the same. Specifically, one aspect of the present invention provides: A nozzle attached to a cylinder of an injection molding machine that injects a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, the nozzle having a capillary hole having an injection port and a melt supply part that is fluidly connected to the capillary hole and supplies a melt to be injected, the nozzle hole diameter of the capillary hole being 4.0 mm or less, and satisfying the following formula: Cross-sectional area change rate = S X / s / X [In formula: Sx is the cross-sectional area of ​​the melt supply section at a position X mm from the connection section (mm 2 ) and; s is the cross-sectional area of ​​the capillary hole at the connection (mm 2 ) and; X is the distance from the connecting part C between the capillary hole 1 and the melt supply part 2 in the nozzle axial direction (the direction of the arrow U in the figure) toward the upstream side of the melt flow, and is specifically 1.4 mm. -1 Thus, a nozzle is provided in which the melt supply is configured to receive a premelt and impart elongational strain to the premelt to form a melt for injection.

[0200] Another aspect of the present invention is an injection molding unit with a nozzle attached to an injection molding machine that injects a thermoplastic resin mixture containing a first component containing a thermoplastic resin and a second component containing one or more selected from the group consisting of a thermoplastic resin and a filler, the injection molding unit with a nozzle having a nozzle portion and a cylinder portion, the nozzle portion having a capillary hole portion having an injection outlet, and a melt supply portion that is fluidly connected to the capillary hole portion and supplies a melt to be injected, the nozzle hole diameter of the capillary hole portion is 4.0 mm or less, and the following formula: Pore ​​diameter change rate=D X / d / X [In formula: Dx is the nozzle hole diameter (mm) of the melt supply part at a position X mm from the connection part; d is the capillary pore diameter at the junction (mm); X is the distance from the connecting portion C between the capillary hole 1 and the melt supply portion 2 toward the upstream side of the melt flow in the nozzle axial direction (the direction of the arrow U in the figure), specifically 1.4 mm. The rate of change in hole diameter is calculated as 2 mm -1 Thus, a nozzle-equipped injection unit is provided, in which a melt supply is configured to receive a premelt and to impart an elongational strain to the premelt to form a melt for injection. EXAMPLES

[0201] The following examples further illustrate exemplary aspects of the present invention, but the present invention is not limited to these examples.

[0202] <Configuration of injection molding machine> Injection molding machine: Sodick "LA60" Plasticization / injection method: Screw pre-plasticization method Screw and plunger diameter: 28mm Plunger stroke: 135mm Maximum injection pressure: 240MPa Maximum injection speed: 500mm / sec Theoretical injection capacity: 83cm 3

[0203] <Nozzle specifications> A capillary nozzle having the following specifications was prepared. The above dimensions were measured and calculated based on the nozzle design drawings. Material: SKD61

[0204] [Table 1]

[0205] <Ingredients> Details of the raw materials used in the examples are given below. Polyamide 6 (hereinafter referred to simply as PA6) UBE Nylon 1013B (manufactured by Ube Industries, Ltd.) Carboxyl end group ratio: ([COOH] / [total end groups]) = 0.6 Viscosity number (VN) of polyamide measured in 96% by weight sulfuric acid = 95 Melting point: 225°C (peak top temperature measured using a differential scanning calorimeter (DSC) (manufactured by PerkinElmer) at a heating rate of 10°C / min. The same applies below.) Polyamide 66 (PA66) Leona 1200 (manufactured by Asahi Kasei Corporation) Viscosity number (VN) of polyamide measured in 96% by weight sulfuric acid = 120 Melting point = 265℃ Polyamide 12 (PA12) Ubesta 3020U (manufactured by Ube Industries, Ltd.) Viscosity number (VN) of polyamide measured in 96% by weight sulfuric acid = 190 Melting point = 179 °C Polypropylene (PP) Homopolypropylene Density=0.90g / cm 3 MFR=35g / 10min (230℃, 21.2N load) Melting point = 160 °C Polyphenylene Ether (PPE) Poly(2,6-dimethyl-1,4-phenylene ether) Reduced viscosity = 0.42 dl / g Glass transition point = 210°C (The peak top temperature of the loss modulus measured on a press-molded test piece using a viscoelasticity measuring device at a heating rate of 10°C / min from 23°C and a frequency of 50Hz. The same applies below to the glass transition point.)

[0206] Maleic anhydride modified polyphenylene ether (mPPE) [Preparation Example 1] 2 parts by mass of maleic anhydride (Crystal MAN-AB: NOF Corp.) was added to 100 parts by mass of PPE and mixed, and the cylinder temperature of the twin screw extruder ZSK26MC with L / D=48 was set to 320°C for C1-4, 280°C for C5-C10 and the die head, and extrusion was performed at a screw rotation speed of 280 rpm. Degassing was performed at the position of C9 to remove the remaining solvent and unreacted maleic anhydride. Here, the screw design was configured such that a screw having the function of melting the resin was arranged in the part of C3, and a screw having the function of interface renewal for modifying the resin was arranged in the parts of C6 and C8. The extruded strand was cooled and then cut to obtain pellet-shaped mPPE with a diameter of 2.5-3.0 mm. The MAH addition rate was measured to be 1.9% by mass. The glass transition point of this mPPE was 208°C.

[0207] Polyphenylene sulfide (PPS) Linear type poly(p-phenylene sulfide) Melt viscosity: 110 Pa·s (shear rate 100 sec -1 , 300℃) Oligomer content: 0.3% by mass Melting point = 278 °C Block copolymer of maleic anhydride modified aromatic vinyl compound and conjugated diene compound (mSBS) Tufprene T912 (manufactured by Asahi Kasei Corporation) Bound styrene content = 40% by mass Maleic anhydride addition rate = 0.2 mass% Glass transition temperature = 92℃ Maleic anhydride modified ethylene-octene copolymer (mEOR) Fusabond MN-493D (made by DowDuPont) MFR(190℃, 2.16kgf)=1.2g / 10min Octene content = 28% by mass Melting point = 55 °C Maleic anhydride addition rate = 1.0 mass% Partially hydrogenated aromatic vinyl compound and conjugated diene block copolymer (SEBS-1) Tuftec H1043 (manufactured by Asahi Kasei Corporation) MFR(230℃, 2.16kgf)=5.0g / 10min Aromatic vinyl compound content: 30% by mass Hydrogenation rate: 98% or more Glass transition temperature = 95℃ Partially hydrogenated aromatic vinyl compound and conjugated diene block copolymer (SEBS-2) Kraton G1650 (made by Kraton Polymers) Aromatic vinyl compound content: 30% by mass Hydrogenation rate: 98% or more Polystyrene equivalent number average molecular weight: 100,000 Glass transition temperature = 95℃

[0208] Maleic anhydride modified SEBS (mSEBS) [Preparation Example 2] 100 parts by mass of SEBS-1 were mixed with 2 parts by mass of maleic anhydride and 0.1 parts by mass of Perbutyl D as a peroxide, and a modification reaction was carried out in a 30 mm twin-screw extruder (L / D=35) at a temperature setting of 200°C. The product was obtained as pellets. The maleic anhydride addition rate of the obtained product was measured and found to be 1.3% by mass. The glass transition point of the obtained product was 92°C. The screw rotation speed was 200 rpm. Styrene / glycidyl methacrylate copolymer (SG) Contains 5% by weight of glycidyl methacrylate Weight average molecular weight: 110,000 Glass transition temperature = 92℃

[0209] Hydrophobized cellulose nanofiber powder (CNF) [Preparation Example 3] The raw material, linter pulp, was stirred in dimethyl sulfoxide (DMSO) at room temperature for 1 hour at 500 rpm using a single-shaft mixer (Imex DKV-1 φ125 mm dissolver).The mixture was then fed to a bead mill (Imex NVM-1.5) using a hose pump and circulated for 120 minutes using only DMSO to obtain a defibrated slurry.

[0210] Then, 11 parts by mass of vinyl acetate and 1.63 parts by mass of sodium bicarbonate were added to the bead mill device per 100 parts by mass of the defibrated slurry, and the device was further circulated for 60 minutes to obtain a hydrophobized cellulose nanofiber slurry.

[0211] During circulation operation, the rotation speed of the bead mill was 2500 rpm and the peripheral speed was 12 m / s. The beads used were made of zirconia and had a diameter of 2.0 mm, and the filling rate was 70% (the slit gap of the bead mill at this time was 0.6 mm). During circulation operation, the slurry temperature was controlled at 40°C using a chiller to absorb heat generated by friction.

[0212] The obtained hydrophobized cellulose nanofiber slurry was mixed with 192 parts by mass of pure water per 100 parts by mass of the defibrated slurry, and then concentrated in a dehydrator. The obtained wet cake was dispersed again in the same amount of pure water, stirred, and concentrated, and this washing procedure was repeated a total of five times.

[0213] The properties of the obtained hydrophobized cellulose nanofiber wet cake were evaluated by the following method, and the diameter was 65 nm, the L / D was 30 or more (approximately 450), the weight average molecular weight (Mw) was 340,000, and the degree of acetylation was 0.9.

[0214] (Diameter and L / D of hydrophobized cellulose nanofibers) First, the wet cake was added to tert-butanol, and further dispersed using a mixer or the like until no aggregates were formed. The concentration was adjusted to 0.5% by mass per 0.5 g of cellulose nanofiber solid content. 100 g of the resulting tert-butanol dispersion was filtered on filter paper, dried at 150°C, and then the filter paper was peeled off to obtain a sheet. The air resistance of this sheet was 10 g / m2. 2 The porous sheets with a permeability of 100 sec / 100 ml or less were used as measurement samples. The basis weight W (g / m2) of the sample left standing for one day in an environment of 23°C and 50% RH 2 After measuring the air permeability, the air permeability resistance R (sec / 100ml) was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model EG01). 2 The value per unit area was calculated. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10

[0215] The wet cake was diluted to 0.01% by mass with tert-butanol, dispersed using a high-shear homogenizer (IKA, product name "Ultra Turrax T18") at 25,000 rpm for 5 minutes, cast onto mica, air-dried, and measured with a high-resolution scanning electron microscope. The magnification was adjusted so that at least 100 cellulose fibers could be observed, and the length (L), major axis (D), and ratio of these were determined for 100 randomly selected cellulose fibers, and the arithmetic average of the 100 cellulose fibers was calculated.

[0216] (Mw of hydrophobized cellulose nanofiber) 0.88 g of the porous sheet was weighed, cut into small pieces with scissors, lightly stirred, 20 mL of pure water was added, and left for one day. Next, the water and solids were separated by centrifugation. Next, 20 mL of acetone was added, lightly stirred, and left for one day. Next, the acetone and solids were separated by centrifugation. Next, 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated again by centrifugation, and then 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated by centrifugation, and 19.2 g of N,N-dimethylacetamide solution prepared so that lithium chloride was 8 mass percent was added to the solids, and the mixture was stirred with a stirrer and visually confirmed to be dissolved. The solution in which cellulose was dissolved was filtered through a 0.45 μm filter, and the filtrate was used as a sample for gel permeation chromatography. The apparatus and measurement conditions used are as follows. Equipment: Tosoh HLC-8120 Column: TSKgel SuperAWM-H (6.0mm I.D. x 15cm) x 2 Detector: RI detector Eluent: N,N-dimethylacetamide (lithium chloride 0.2%) Flow rate: 0.6mL / min Calibration curve: Pullulan conversion

[0217] (Degree of acetylation of hydrophobized cellulose nanofiber) The infrared spectrum of the porous sheet at five points was measured by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Co., Ltd.) The infrared spectrum measurement was performed under the following conditions. Accumulation count: 64 times, Wavenumber resolution: 4cm -1 , Measurement wave number range: 4000~600cm -1 , ATR crystal: Diamond, Incident angle: 45° From the obtained IR spectrum, the IR index was calculated using the following formula: IR index = H1730 / H1030 In the formula, H1730 and H1030 are at 1730 cm -1 , 1030cm -1 (absorption band of CO stretching vibration of cellulose backbone chain) -1 and 1500cm -1 The line connecting the -1 and 1500cm -1 The line connecting these points is taken as the baseline, and the absorbance is calculated when this baseline is taken as 0. The average degree of substitution at each measurement site was calculated from the IR index according to the following formula, and the average value was taken as DS. DS = 4.13 × IR index

[0218] PEG20000 was added to the obtained aqueous dispersion of hydrophobic cellulose nanofiber (solid content: 10% by mass) in an amount of 5 parts by mass per 100 parts by mass of hydrophobic cellulose nanofiber, and then the mixture was vacuum dried at approximately 40°C using a revolution / rotation type mixer (EME V-mini300) to obtain hydrophobic cellulose nanofiber powder (CNF).

[0219] Carbon Black (CB) Ketjenblack EC600JD (manufactured by Lion Corporation)

[0220] <Examples A1 to A5 and Comparative Examples A1 to A2 (Single-screw extrusion products)> [Raw material pellet preparation process] 80 parts by mass of PA6 as the first component and 20 parts by mass of mSBS as the second component were dry blended to prepare a pellet mixture for extrusion. A double dulmage type screw was attached to a 32 mm screw single-screw extruder with an L / D of 24, and the cylinder temperatures were set to 230°C for cylinder 1, 245°C for cylinders 2-3 and the die head, and the extrusion process was performed at a screw rotation speed of 75 rpm. The strand from the die head was cooled and cut to obtain pellets. The double dulmage was located in the latter half of C2, and vacuum suction was performed from the vacuum degassing port of C3.

[0221] [Injection molding process] Molding was carried out using the pellets obtained in the raw material pellet preparation process. The nozzle at the tip of the cylinder of the LA-60 injection molding machine was changed to the nozzle type shown in Table 1, and the nozzle part, the plunger tip part and center part, and the screw plasticization part were each set to 250°C (i.e., the melting temperature when forming the pre-molten body of the present disclosure, the same applies below), and the rear end part of the plunger was set to 235°C.

[0222] Injection molding was performed under these conditions to obtain ISO multipurpose test pieces. The injection speed was set to 150±50 mm / sec so that the raw material pellet melt (pre-melt) would pass through the nozzle shown in Table 1 to form an injection molded body imparted with elongation strain (for each Example) or shear strain (for each Comparative Example). All examples using the same raw material pellets were molded at the same injection speed. The mold temperature was set to 80°C.

[0223] The dispersed particle diameters of the dispersed phase (in this case, the mSBS phase) in the obtained injection-molded test pieces and the raw material pellets were measured. (Measurement of dispersed particle size by chloroform etching) The dispersed particle diameter was measured by cutting a cross section from a part of the pellet or molded piece with a microtome, immersing it in chloroform, which can dissolve the dispersed phase, and observing the treated sample with a scanning electron microscope. The diameters of at least 50 random holes were measured, and the diameters were measured from the maximum diameter to the minimum diameter to obtain an index of particle size distribution, and the dispersed particle diameters were compared based on the number average particle diameter of the 50 holes. Since the components of the dispersed phase were extracted with chloroform, the dispersed particle diameter in the raw material pellets can be regarded as the dispersed diameter of the dispersed phase in the pre-melt of the present disclosure.

[0224] The multipurpose test pieces thus obtained were used to measure the tensile elongation (in accordance with ISO 527-1,2) and Charpy impact strength (in accordance with ISO 179-1 / 1eA) at 23°C and a crosshead speed of 5 mm / min.

[0225] Comparing Example A4 with Comparative Examples A1 and A2, it is found that the number of large particles in the particle size distribution is reduced by increasing the angle (θ) that the hole wall of the melt supply part makes with respect to the direction parallel to the nozzle axis and toward the upstream of the melt flow. Furthermore, comparing Examples A1 to A3, it is found that the particle size becomes very fine and the distribution is narrowed by increasing the hole size change rate and cross-sectional area change rate.

[0226] However, in Example A2, some black spots were observed on the surface of the molded piece when continuous molding was continued. It is presumed that this is because θ exceeded 90°, resulting in stagnation areas.

[0227] <Examples A6 to A8 and Comparative Examples A3 to A4 (Twin-screw extrusion products)> [Raw material pellet preparation process] The same procedure as in Example A1 was carried out except that the extruder was changed to a twin screw extruder ZSK26MC with L / D=48, the cylinder temperatures were set to 230°C for C1 to C5 and 250°C for C6 to C10, the screw rotation speed was 200 rpm, and degassing under reduced pressure was carried out at position C9. Here, the screw design was configured such that a screw having the function of melting the resin was arranged at the C5 portion, and a screw having the function of dispersing and mixing the resin was arranged at the C7 portion.

[0228] [Injection molding process] The same procedure as in Example A1 was carried out. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed. The twin-screw extrusion material had a smaller dispersed particle size than the single-screw extrusion material, but the nozzle shape allowed for similarly small particle size and narrow distribution. It is interesting that when a nozzle with a high rate of change in hole size and cross-sectional area was used, the same dispersed size was obtained even with different raw materials. However, in the case of the twin-screw extrusion material, the physical properties tended to be slightly worse than those of the single-screw extrusion material. Although the details are unknown, it is thought that this is because the twin-screw extrusion material was subjected to a crosslinking reaction at the double bonds of the SBS component due to the high thermal history during the extrusion process, reducing its flexibility.

[0229] [Table 2]

[0230] <Examples A9 to A11 and Comparative Example A5 (Diluted Masterbatch)> [Raw material pellet preparation process] 30 parts by mass of PA6 and 20 parts by mass of mSBS were dry-blended to prepare a pellet mixture for extrusion. Except for changing the screw of the extruder to a single Dulmage type screw, the same procedure was followed as in Example A1 to obtain a high-concentration elastomer master batch (PA6 / SBS-MB).

[0231] [Injection molding process] The same procedure as in Example A1 was carried out, except that the first component was changed to 50 parts by mass of PA6, and the second component was changed to 50 parts by mass of a dry blend of PA6 / SBS-MB pellets obtained in the raw material pellet preparation process. The nozzle type of the molding machine was as shown in the table, thereby forming an injection molded article to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted.

[0232] In this study, the nozzle shape also caused the particle size to become smaller and the distribution to become narrower. Furthermore, when a nozzle with a high rate of change in hole diameter and cross-sectional area was used, the dispersed diameter tended to be roughly the same even if the raw material was different.

[0233] <Examples A12 to A13 and Comparative Example A6 (Pellet Blend)> [Raw material pellet preparation process] Not implemented. [Injection molding process] The same procedure as in Example A1 was carried out except that the pellets obtained in the raw material pellet preparation process were changed to a pellet dry blend product containing 80 parts by mass of PA6 as the first component and 20 parts by mass of mSBS as the second component. The nozzle type of the molding machine was as shown in the table, thereby forming an injection molded article to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted.

[0234] In this example, the prior melt-kneading was omitted and the pellets of the two-component blend were directly introduced into the injection molding machine, so the measured diameter of the pellets of the second component itself was regarded as the particle diameter of the dispersed phase in the premelt.

[0235] This study shows that when a nozzle with a high rate of change in hole diameter and cross-sectional area is used, a uniform dispersed phase with an extremely small distribution is obtained. This is thought to be because the heat history of the extrusion process is eliminated, suppressing the increase in viscosity of the dispersed phase. In addition, the highest physical properties are also shown, which is presumably due to the effect of reducing the heat history.

[0236] <Examples A14 to A15 and Comparative Example A7 (Single-screw extrusion product)> [Raw material pellet preparation process] 85 parts by mass of PA66 as the first component and 15 parts by mass of mEOR as the second component were dry blended, and the cylinder temperatures of the extruder were set to 260°C for cylinders 1 and 2, and 280°C for cylinder 3 and the die head. All other conditions were the same as in Example A1. [Injection molding process] The same procedure as in Example A1 was carried out. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed.

[0237] <Examples A16 to A17 and Comparative Example A8 (Single-screw extrusion product)> [Raw material pellet preparation process] 85 parts by mass of PA12 as the first component, 7.5 parts by mass of SEBS-1 as the second component, and 7.5 parts by mass of mSEBS were dry blended, and the cylinder temperature settings of the extruder were all set to 220°C. All other operations were carried out in the same manner as in Example A1. [Injection molding process] The same procedure as in Example A1 was carried out. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed.

[0238] [Table 3]

[0239] <Examples A18 to A19 and Comparative Example A9 (Single-screw extrusion product)> [Raw material pellet preparation process] The raw material pellets of Example A1 were used. [Injection molding process] Molding was performed using the same injection molding machine as in Example A1, but with the nozzle changed to the nozzle type shown in Table 4, and the injection speed changed to the speed shown in Table 4. The maximum injection pressure obtained at this time is also shown in Table 4. All other operations were performed in the same manner as in Example A1. In this way, an injection molded body to which an elongation strain (for each Example) or a shear strain (for each Comparative Example) was imparted was formed.

[0240] [Table 4]

[0241] <Examples B1 to B5 and Comparative Examples B1 to B2 (Twin-screw extrusion products)> [Raw material pellet preparation process] The cylinder temperature of the twin-screw extruder ZSK26MC with L / D=48 was set to 320 ° C for C1 to 4, and 280 ° C for C5 to C10 and the die head, and 30 parts by mass of mPPE and 10 parts by mass of SEBS-2, which are the second component, were fed from the upstream raw material feed port, and 60 parts by mass of PA6, which is the first component, was fed from the downstream raw material feed port (side feed port) installed in C5, melt-kneaded, and the strand from the die head was cooled and cut to obtain pellets. At this time, the screw rotation speed was set to 300 rpm, and degassing under reduced pressure was performed at the position of C9. Here, the screw design was configured to have a screw having the function of melting the resin in the part of C3, and a screw having the function of dispersing and mixing the resin in the parts of C6 and C8.

[0242] [Injection molding process] The pellets obtained in the raw material pellet preparation step were used for molding.

[0243] Molding was carried out in the same manner as in Example A1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 280°C, and the rear end of the plunger was set to 255°C. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body was formed to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted.

[0244] In addition, flat molded specimens with a length of 90 mm, a width of 50 mm, and a thickness of 2.5 mm were also prepared in a separate process for measuring low-temperature surface impact strength. The injection molding conditions were the same as those for obtaining the multipurpose test specimens.

[0245] The dispersed particle diameters of the obtained multipurpose test piece and the dispersed phase (in this case, the phase consisting of mPPE and SEBS-2) in the raw material pellets were measured by etching the dispersed phase with chloroform, as in Example A1.

[0246] The multipurpose test specimens thus obtained were used to measure tensile elongation at 23° C. and a crosshead speed of 5 mm / min, and the flat molded specimens were used to measure low-temperature surface impact strength.

[0247] (Measurement of low-temperature surface impact strength) The low-temperature lateral impact strength was measured by placing the flat molded pieces in a low-temperature thermostatic chamber set at -30℃ for 2 hours to sufficiently cool them, then removing them and quickly measuring them using a graphic impact tester set under the following conditions: sample holder diameter 40mm, striker diameter 12.7mm, load 6.5kg, and striker impact speed on the sample 5m / sec. The lateral impact strength was expressed as the total absorbed energy, which is the sum of the crack initiation energy and the propagation energy. Ten pieces were measured at each time, and the average value was calculated from each value.

[0248] Comparing Example B4 with Comparative Examples B1 and B2, it is found that the number of large particles in the particle size distribution is reduced by increasing the nozzle angle θ. Furthermore, comparing Examples B1 to B3, it is found that the particle size becomes very fine and the distribution is narrowed by increasing the hole size change rate and the cross-sectional area change rate.

[0249] However, in Example B2, when continuous molding was continued, some black spots were observed on the surface of the molded pieces. This phenomenon was somewhat more frequent than in Example A2. This is also thought to be due to the influence of carbonized material in the retained areas.

[0250] Even though the same raw materials were used, the tensile elongation and low-temperature dart impact strength were dramatically improved by increasing the nozzle θ and increasing the hole diameter change rate and cross-sectional area change rate. This is believed to be due to the uniformly miniaturized dispersed particle size as mentioned above.

[0251] <Examples B6 to B8 and Comparative Examples B3 to B4 (Diluted Masterbatches)> [Raw material pellet preparation process] The cylinder temperature of the twin-screw extruder ZSK26MC with L / D=48 was set to 320 ° C for C1 to C4, and 280 ° C for C5 to C10 and the die head, and 30 parts by mass of mPPE and 10 parts by mass of SEBS-2, which are the second components, were fed, melt-kneaded, and the strands from the die head were cooled and cut to obtain master batch pellets (particle size: 2.5 to 3.0 mm) of polyphenylene ether, partially hydrogenated aromatic vinyl compound, and conjugated diene compound block copolymer. At this time, the screw rotation speed was 250 rpm, and degassing was performed at the position of C9 under reduced pressure. Here, the screw design was configured to have a screw having the function of melting the resin in the C3 portion, and a screw having the function of dispersing and mixing the resin in the C6 and C8 portions.

[0252] [Injection molding process] The same procedure as in Example B1 was carried out, except that 60 parts by mass of PA6 as the first component and 40 parts by mass of the pellets obtained in the raw material pellet preparation step as the second component were dry blended. The nozzle type of the molding machine was as shown in the table. As a result, an injection molded body to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted was formed.

[0253] In this example, the particle size of the dispersed phase before injection molding is the size of the raw material pellets, so the measured size of the pellets of the second component themselves was regarded as the particle size of the dispersed phase in the pre-melt.

[0254] Normally, it is difficult to finely disperse a dispersed phase containing a high concentration of PPE and a polyamide with a low melt viscosity by injection molding alone. However, it is found that by using a nozzle with a large θ and a high rate of change in hole diameter and cross-sectional area, a uniform dispersed phase with an extremely small distribution can be obtained, imparting high physical properties.

[0255] <Examples B9 to B11 and Comparative Example B5 (twin-screw extrusion product)> [Raw material pellet preparation process] The cylinder temperature of the twin-screw extruder ZSK26MC with L / D=48 was set to 230°C for C1 to C4, and 280°C for C5 to C10 and the die head, and 70 parts by mass of PP and 10 parts by mass of mSEBS, which are the second component, were fed from the upstream raw material feed port, and 20 parts by mass of PA6, which is the first component, was fed from the downstream raw material feed port (side feed port) installed in C5, and melt-kneaded, and the strand from the die head was cooled and cut, and obtained as pellets. The conditions and screw design at this time were the same as those in Example B1.

[0256] [Injection molding process] The pellets obtained in the raw material pellet preparation step were used for molding. Molding was carried out in the same manner as in Example B1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 270°C, and the rear end of the plunger was set to 235°C. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed. The dispersed particle diameter of the dispersed phase (in this case, the PA phase) in the obtained multipurpose test piece and the raw material pellets was measured.

[0257] (Measurement of particle size of PA phase in raw material pellets) The test pieces were smoothed using a microtome, the sections were stained with phosphotungstic acid, thoroughly washed with water, and observed using a scanning electron microscope with energy dispersive X-ray spectroscopy (EDX method). The shading was measured by image analysis. The diameters of at least 100 randomly selected PA phases were measured.

[0258] The multi-purpose test specimens thus obtained were used to measure tensile elongation at 23° C. and a crosshead speed of 5 mm / min, and the flat molded specimens were used to measure low-temperature surface impact strength. The methods were the same as those used in Example B1.

[0259] <Examples B12 to B14 and Comparative Example B6 (Masterbatch Blend)> [Raw material pellet preparation process] The cylinder temperature of the twin screw extruder ZSK26MC with L / D=48 was set to 300°C for C1 to C4, and 280°C for C5 to C10 and the die head, and 55 parts by mass of PPS and 10 parts by mass of SG were fed, melt-kneaded, and the strand from the die head was cooled and cut to obtain PPS / SG-MB pellets (pellet diameter: 2.9 to 3.2 mm) consisting of PPS and SG. At this time, the screw rotation speed was set to 300 rpm, and degassing was performed at the position of C9 under reduced pressure. Here, the screw design was configured such that a screw having the function of melting the resin was arranged in the part of C3, and screws having the function of dispersing and mixing the resin were arranged in the parts of C6 and C8.

[0260] In addition, the extruder temperatures were set to 320°C for C1 to C4, and 280°C for C5 to C10 and the die head, and the same procedures were carried out as for the PPS / SG-MB pellets, except that 25 parts by mass of PPE and 10 parts by mass of SEBS-2 were supplied, to obtain PPE / SEBS-2-MB pellets (pellet diameter: 2.5 to 2.8 mm) consisting of PPE and SEBS-2.

[0261] [Injection molding process] The pellets obtained in the raw material pellet preparation step were used for molding. 65 parts by mass of PPS / SG-MB pellets as the first component and 35 parts by mass of PPE / SEBS-2-MB pellets as the second component were dry blended.

[0262] Molding was performed in the same manner as in Example B1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 300°C, and the rear end of the plunger was set to 275°C. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted was formed. In addition, the dispersed particle size of the dispersed phase (in this case, the phase consisting of PPE and SEBS-2) in the raw material pellets was also measured in the same manner as in Example B1.

[0263] The multipurpose test specimens thus obtained were used to measure tensile elongation at 23°C and a crosshead speed of 5 mm / min, and flat molded specimens taken under the same conditions as those for obtaining the multipurpose test specimens were used to measure room temperature surface impact strength.

[0264] (Measurement of room temperature surface impact strength) The room temperature lateral impact strength was measured by conditioning the flat molded pieces at 23°C and 50% RH for at least 48 hours, and then using a graphic impact tester set under the following conditions: sample holder diameter 40 mm, striker diameter 12.7 mm, load 6.5 kg, and striker impact speed on the sample 5 m / sec. The lateral impact strength was expressed as the total absorbed energy, which is the sum of the crack initiation energy and the propagation energy. Ten pieces were measured for each test, and the average value was calculated from the respective values.

[0265] By increasing the nozzle angle and increasing the rate of change in hole diameter and cross-sectional area, the particle size was reduced and the distribution narrowed. Although the original impact resistance and elongation were low, the PPS composition still had high physical properties, and the properties were improved to a level that exceeded those of pellets that had been uniformly mixed in an extruder.

[0266] [Table 5]

[0267] [Table 6]

[0268] <Examples C1 to C4 and Comparative Examples C1 to C2 (Twin-screw extrusion products)> [Raw material pellet preparation process] The cylinder temperature of the twin screw extruder ZSK26MC with L / D=48 was set to 260°C for C1 to C4, and 240°C for C5 to C10 and the die head, and 90 parts by mass of PA6 as the first component and 10 parts by mass of CNF as the second component were fed, melt-kneaded, and the strands from the die head were cooled and cut to obtain pellets. At this time, the screw rotation speed was set to 400 rpm, and degassing was performed at the position of C9. Here, the screw design was configured such that a screw having the function of melting the resin was arranged in the part of C3, and screws having the function of dispersing and mixing the resin were arranged in the parts of C6 and C8.

[0269] [Injection molding process] The pellets obtained in the raw material pellet preparation step were used for molding. Molding was carried out in the same manner as in Example A1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 250°C, and the rear end of the plunger was set to 225°C. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed. The number of CNF aggregates in the obtained multipurpose test piece and the dispersed particles (CNF in this case) in the raw material pellets was measured.

[0270] (Measurement of CNF aggregate number, average aggregate size, and aggregate size distribution) CT measurement was performed on the measurement object using a high-resolution 3D X-ray microscope (nano3DX: manufactured by Rigaku Corporation) under conditions of X-ray tube voltage 40 kV, tube current 30 mA, and 600 cubic μm. The number of projections was 1000, and the exposure time was 24 seconds per image. The spatial resolution at this time was 0.54 μm / pixel. The obtained data was binarized using the Otsu method. This measurement was performed on three different sites, and the number of aggregates detected was counted and arithmetically averaged. In addition, the particle diameter data of each aggregate obtained was arithmetically averaged to calculate the average aggregate diameter, and the ratio (d75% / d25%) of the 25% aggregate diameter (d25%) and the 75% aggregate diameter (d75%) from the smallest aggregate diameter was calculated to obtain the aggregate diameter distribution. In addition, when measuring the aggregate diameter, the data of the circle equivalent diameter is used as a substitute for flat aggregates having a major axis and a minor axis. Using the obtained multipurpose test piece, the tensile elongation measured at 23° C. and a crosshead speed of 5 mm / min and the thermal expansion coefficient as an index of thermal expandability were measured.

[0271] (Measurement of thermal expansion coefficient) The thermal expansion coefficient was measured by cutting a sample of 10 mm in length, 4 mm in width, and 2 mm in thickness from the center of the multipurpose test piece using a precision cut-off saw, measuring the expansion rate in the direction of resin flow during molding (MD direction, length direction of the sample) at a measurement temperature range of -10°C to 120°C, and calculating the thermal expansion coefficient between 20°C and 100°C. Prior to the measurement, the sample was left to stand in a 120°C environment for 5 hours for annealing.

[0272] In Comparative Examples C1 and C2, no significant difference was observed between the number of aggregates in the raw material pellets and in the molded product, but in Examples C1 and C2, which used the same raw material but increased the nozzle θ while increasing the rate of change in hole diameter and cross-sectional area, the phenomenon was confirmed in which the tensile elongation showed yield and the thermal expansion coefficient decreased. This is thought to be due to the fact that the CNF was finely dispersed by the reduction in the number of aggregates, which did not cause breakage and suppressed the expansion of the resin.

[0273] <Examples C5 to C7 and Comparative Example C3 (diluted masterbatch)> [Raw material pellet preparation process] The cylinder temperature of the twin screw extruder ZSK26MC with L / D=48 was set to 260°C for C1-4, 240°C for C5-C10 and the die head, 70 parts by mass of PA6 and 30 parts by mass of CNF were fed, melt-kneaded, and the strand from the die head was cooled and cut to obtain pellets as the second component. At this time, the screw rotation speed was set to 300 rpm, and degassing was performed at the position of C9. Here, the screw design was configured such that a screw having the function of melting the resin was arranged in the part of C3, and a screw having the function of dispersing and mixing the resin was arranged in the parts of C6 and C8. The number of aggregates in the master batch pellets obtained here was measured by the method described in Example C1, and was very large at an average of 60.7.

[0274] [Injection molding process] The second component obtained in the raw material pellet preparation process was diluted and molded with PA6 as the first component so that the CNF concentration was 10%.

[0275] Injection molding was performed in the same manner as in Example C1. The nozzle type of the molding machine was as shown in the table. In this way, injection molded bodies with elongation strain (for each Example) or shear strain (for each Comparative Example) were formed.

[0276] As in Example C1, the number of CNF aggregates, tensile elongation, and thermal expansion coefficient in the multipurpose test specimen were measured.

[0277] In Comparative Examples C3 and C4, the tensile elongation did not show yield and the thermal expansion coefficient was high, but in Examples C5 and C6, in which the nozzle θ was increased while the hole diameter change rate and the cross-sectional area change rate were increased, the tensile elongation showed yield and the thermal expansion coefficient was at a numerically better level than Examples C1 and C2, which were pre-mixed in an extruder.

[0278] <Examples C8 to C10 and Comparative Example C4 (diluted masterbatch)> [Raw material pellet preparation process] The procedure was carried out similarly to Example C5. [Injection molding process] The second component obtained in the raw material pellet preparation process was diluted and molded with PA6 as the first component so that the CNF concentration was 5%. Injection molding was performed in the same manner as in Example C1, and the number of CNF aggregates in the multipurpose test piece, the tensile elongation, and the thermal expansion coefficient were measured. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body with elongation strain (for each Example) or shear strain (for each Comparative Example) was formed.

[0279] The trend did not change even when the CNF concentration was changed.

[0280] <Examples C11 to C12 and Comparative Example C5 (Diluted Masterbatch)> [Raw material pellet preparation process] The cylinder temperature of the twin screw extruder ZSK26MC with L / D=48 was set to 220°C for C1-4, 170°C for C5-C10 and the die head, 70 parts by mass of PP and 30 parts by mass of CNF were fed, melt-kneaded, and the strand from the die head was cooled and cut to obtain pellets as the second component. At this time, the screw rotation speed was 400 rpm, and degassing was performed at the position of C9. Here, the screw design was configured such that a screw having a function of melting the resin was arranged in the part of C3, and a screw having a function of dispersing and mixing the resin was arranged in the parts of C6 and C8. The number of aggregates in the master batch pellets obtained here was measured by the method described in Example C1, and was very poor, exceeding 100 on average.

[0281] [Injection molding process] The second component obtained in the raw material pellet preparation step was diluted and molded with PP6 as the first component so that the CNF concentration was 5% by mass. Molding was performed in the same manner as in Example C1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 220°C, and the rear end of the plunger was set to 180°C. The number of CNF aggregates in the multipurpose test piece, tensile elongation, and thermal expansion coefficient were measured. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body with elongation strain (for each example) or shear strain (for each comparative example) was formed.

[0282] Although there were differences in the number of aggregates and physical properties due to the change in the continuous phase resin to PP, the tendency in nozzle molding was the same.

[0283] [Table 7]

[0284] [Table 8]

[0285] <Examples D1 to D4 and Comparative Examples D1 to D2 (Twin-screw extrusion products)> [Raw material pellet preparation process] The cylinder temperature of the twin-screw extruder ZSK26MC with L / D=48 was set to 280 ° C for C1 to 4, and 300 ° C for C5 to C10 and the die head, and 60 parts by mass of PA66 was fed from the upstream raw material feed port, and 30 parts by mass of PA66 and 10 parts by mass of CB were fed from the downstream raw material feed port (side feed port) installed in C5, melt-kneading was performed, and the strand from the die head was cooled and cut to obtain PA / CB-MB pellets as the second component. At this time, the screw rotation speed was set to 300 rpm, and degassing was performed at the position of C9 under reduced pressure. Here, the screw design was configured to have a screw having the function of melting the resin in the part of C3, and a screw having the function of dispersing and mixing the resin in the parts of C6 and C8.

[0286] (Measurement of the number of CB aggregates, average aggregate size, and aggregate size distribution) To measure the amount of CB aggregates in the PA / CB-MB pellets obtained here, a reflected light optical microscope (PME3: manufactured by Olympus Corporation) was used to observe the dispersion state of carbon black on the smooth surface of the observation sample at a magnification of 100 times, photographs were taken, and the images were scanned and converted into digital images with a resolution of 400 dpi. The number of secondary aggregates of carbon black was counted within the field of view of the obtained digital images. Ten photographs (total field of view: 10 mm) were taken. 2 ) and the average value was calculated. In addition, the particle size data of each aggregate obtained was arithmetically averaged to calculate the average aggregate size, and the ratio (d75% / d25%) of the 25% aggregate size (d25%) and the 75% aggregate size (d75%) from the smallest aggregate size was calculated to obtain the aggregate size distribution. In this aggregate size measurement, for flat aggregates having a major axis and a minor axis, the average of the major axis and the minor axis was used as the aggregate size. The results obtained are shown in Table 9.

[0287] Next, the cylinder temperature of the ZSK26MC extruder was set to 320 ° C for C1 to 4, and 280 ° C for C5 to C10 and the die head, and 30 parts by mass of mPPE and 10 parts by mass of SEBS-2 were fed from the upstream raw material feed port as the first component, and 40 parts by mass of PA66 as the first component and 10 parts by mass of PA / CB-MB pellets as the second component were fed from the downstream raw material feed port (side feed port) installed in C5, melt kneading was performed, and the strands from the die head were cooled and cut to obtain pellets. At this time, the screw rotation speed was set to 320 rpm, and degassing was performed at the position of C9 under reduced pressure. Here, the screw design is the same as that used for PA / CB-MB.

[0288] [Injection molding process] The pellets obtained in the raw material pellet preparation step were used for molding. Molding was carried out in the same manner as in Example B1, except that the nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 290°C, and the rear end of the plunger was set to 280°C. The nozzle type of the molding machine was as shown in the table. In this way, an injection molded body having elongation strain (for each Example) or shear strain (for each Comparative Example) was formed.

[0289] The number of CB aggregates in the raw pellets and the obtained multi-purpose test pieces was measured according to the method used for measuring the MB in the raw pellet preparation process.

[0290] The multipurpose test specimen thus obtained was used to measure the notched Charpy impact strength at 23° C. Furthermore, the volume resistivity was measured by the following method.

[0291] (Volume resistivity measurement) The multi-purpose test piece obtained was scratched with a cutter knife and immersed in dry ice / methanol at -75℃ to -70℃ for about 1 hour, then removed and both ends were broken off to obtain a test piece with a uniform cross-sectional area of ​​10×4 mm, length of about 70 mm, and fractured surfaces at both ends. Silver paint was applied to both fractured surfaces, and the surfaces were dried. The volume resistivity between both fractured surfaces was measured with a digital insulation resistance meter [DG525: Sanwa Electric Instruments] at an applied voltage of 250 V. The measurement was performed on five different test pieces, and the arithmetic average was used to determine the volume resistivity.

[0292] The number of CB aggregates in Comparative Examples C1 and C2 is roughly the same as that in the raw pellets, whereas the number of aggregates is significantly reduced in the examples using the nozzle of the present invention.Furthermore, it is found that the conflicting properties of impact strength and electrical conductivity can be improved at the same time.

[0293] <Examples D5 to D7 and Comparative Example D3 (Masterbatch Raw Material)> [Injection molding process] The pellets obtained in the raw material pellet preparation step and other raw materials were mixed and molded. The nozzle, plunger tip and center, and screw plasticizing section of the injection molding machine were set to 290°C, and the rear end of the plunger was set to 280°C. Injection molding was performed using a raw material obtained by dry blending 40 parts by mass of PA66, 30 parts by mass of mPPE, and 10 parts by mass of SEBS-2 as the first component, and 10 parts by mass of PA / CB-MB as the second component. All other conditions were the same as in Example D1. The nozzle type of the molding machine was as shown in the table. As a result, an injection molded body to which elongation strain (for each Example) or shear strain (for each Comparative Example) was imparted was formed.

[0294] The number of CB aggregates in the obtained multipurpose test specimen was measured. Furthermore, the notched Charpy impact strength at 23°C and the volume resistivity were measured using the obtained multipurpose test specimen.

[0295] The number of CB aggregates in Comparative Example D3 corresponds to the number of diluted PA / CB-MB, but it can be seen that the use of the nozzle of the present invention shows the same level of aggregate number and physical properties as the use of a twin-screw extruder and the nozzle of the present invention. This suggests that not only the number of aggregates but also the compatibility in the resin phase was sufficiently performed. In addition, the volume resistivity of the bad sample was not conductive, but the good sample showed good volume resistivity. It is thought that the carbon was unevenly dispersed in the bad sample, although this is not reflected in the number of aggregates.

[0296] [Table 9] [Industrial Applicability]

[0297] The present invention can be suitably applied to the production of a wide range of injection molded articles which may contain a variety of blended components. [Explanation of symbols]

[0298] 1 Capillary hole 2. Melt supply section 11,21 Nozzle 40 Injection unit with nozzle 41 Nozzle section 42 Cylinder section C connection part P injection port W hole wall

Claims

1. A method for producing a molded body of a thermoplastic resin mixture including a first component including a thermoplastic resin and a second component including one or more selected from the group consisting of a thermoplastic resin and a filler, comprising: a first melt forming step of obtaining a first melt containing the first component and the second component; A second melt forming step of dispersing a second component in the first component in the first melt to obtain a second melt; and a molding step of molding the second molten body; Including, In the second molten body forming step, an elongation strain is applied to the first molten body to form the second molten body; The method of claim 1, wherein a dispersion diameter of the second component in the compact is smaller than a dispersion diameter of the second component in the first melt.

2. The method of claim 1 , wherein the first component comprises a crystalline resin and the second component comprises an amorphous resin.

3. 3. The method according to claim 1, wherein in the first melt forming step, the first component and the second component are supplied separately, and then the first component and the second component are melt-kneaded to form the first melt.

4. The method according to any one of claims 1 to 3, wherein each of the first component and the second component comprises a thermoplastic resin and a filler, and the filler content of the first component and the filler content of the second component are different from each other.

Citation Information

Patent Citations

  • Manufacture of resin molding

    JP1989244814A

  • Antistatic resin composition for injection molding

    JP1999043616A

  • Tip nozzle and adapter of injection molding machine

    JP2003200474A

  • Injection molding device

    JP2016175210A